Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Pathogenic mechanisms of Trichoderma hamatum, a postharvest pathogen causing fruit rot - Hai-Rui Wang; Xiong Xiong; Wen-Chao Li; Shuang-Jiao Ma; Yan-Xue Liu; Tong Liu; Ke-Xiang Gao; Chuan-Rong Li; Hui-Xiang Liu; Ye-Han Tian (Postharvest Biology and Technology, 2026)

Competitive hydrated eutectic electrolyte for 9650 h long-lived aqueous Zn-ion batteries with wide-temperature operability - Haowen Xiang; Yan Qin; Kaiwen Zhang; Yao Zhang; Jinda Wang; Rui Zhao; Fushao Li; Xinyue Liang; Xuefeng Zou (Chemical Engineering Journal, 2026)

A hybrid machine learning and data assimilation framework for penman–monteith evapotranspiration estimation over China - Xiaowen Wu; Xiang Li; Jianli Ding; Shaomin Liu; Tongren Xu; Lisheng Song; Sayed M. Bateni; Ziwei Xu; Dongxing Wu; Xinlei He; Jinjie Wang; Rui Liu; et al. (Remote Sensing of Environment, 2026)

Bearing capacity envelopes of wide-shallow bucket foundations in sand under combined horizontal and moment loading - Run Liu; Rui Zhou; Xiang-chuan Meng; Yu Wang (Ocean Engineering, 2026)

Construction of Al/Nd 3D floral hierarchical architecture nanorods incorporated into lamellar structure MgO via self-assembly for photothermal catalytic hydrolysis of COS - Xiaomeng Du; Rui Cao; Xueqian Wang; Jinghao Xiang; Ping Ning; Lijuan Jia (Journal of Environmental Chemical Engineering, 2026)

Mechanical response of layered heterogeneous hydrate-bearing sediments to depressurization - Hua Du; Huie Chen; Fansheng Kong; Qing Wang; Yonggui Luo; Xiang Gao; Jinzhong Zhu; Lanting Fu; Rui Fu (International Journal of Rock Mechanics and Mining Sciences, 2026)

Temperature-responsive topology regulation for fire-safe, high-strength polyamide 66 via a low-barrier phosphonate spacer - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Ya-Dong Wang; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

PBO-reinforced and silane-crosslinked aramid III nanofiber aerogels for high-temperature stability, flame retardancy, and hydrophobic protection - Jiandong Yin; Xinyue Wang; Yunmei Xie; Bin Wang; Guiyan Yang; Ruping Chen; Dong Xiang; Yuanpeng Wu; Tao Peng; Jie Zhang; Chunxia Zhao; Hui Li; et al. (Chemical Engineering Journal, 2026)

Mechanistic insights into the adsorption and separation of nonpolar molecules on delocalization porous carbon: Dispersion interactions enhanced by multiple bonds - Peixin Wang; Jingxu Tian; Da Wei; Yue Sun; Bo Liu; Wenji Pi; Jun Ma; Yunfeng Zhang; Hongyu Chen; Rui Shi; Yang Guo; Xiang Xu; et al. (Chemical Engineering Journal, 2026)

A review of atmospheric black carbon research progress in China - Qi Zhou; Shunyao Wang; Shujun Bie; Junjie Cai; Yingjun Chen; Yuan Cheng; Xiang Ding; Jianwei Gu; Jie Li; Weijun Li; Dantong Liu; Jiaying Liu; et al. (Atmospheric Environment, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Environmental DNA metabarcoding complements bottom trawling and detects fish species beyond recorded ranges in the Chukchi Borderland, Central Arctic Ocean - Hai Li; Fang Yang; Xiang Zhang; Ran Zhang; Rui Wang; Xing Miao; Shigang Liu; Puqing Song; Yuan Li; Longshan Lin (Marine Environmental Research, 2026)

WaveUNet: An efficient deep network based on discrete wavelet transform and attention mechanism for InSAR phase unwrapping - Wenfei Mao; Hongquan Xiang; Xue Cheng; Guoxiang Liu; Xiaowen Wang; Rui Zhang; Oriol Monserrat; Michele Crosetto (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Oxygen demand and behavioral responses of adult largemouth bass (Micropterus salmoides) to intensive aquaculture-related drivers - Hao Fan; Chang Guo; Xiang Lei; Peng Wan; Ming Zhu; Deqing Wang; Rui Song (Aquacultural Engineering, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Decoction-derived bioactive nanoparticles of Lycopodium japonicum Thunb. attenuate knee osteoarthritis by regulating MAPK/ERK signaling - Xiaohui Chen; Gang Liang; Liangwei Wang; Zhilang Xie; Zhongpan Li; Yulin Xiang; Rongzhu Li; Fulan Zhao; Xiaojun Chen; Rui Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

CRISPR/Cas9 system inhibits largemouth bass virus infection in vitro and in vivo - Rui-Long He; Mao-sheng He; Xin-Yuan Jiang; Yi-Wang; Hao-Liang; Xiang-Yi Bu; Kun Xu; Fei Ling; Gao-Xue Wang; Hai-Feng Jiang (Aquaculture, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Construction and evaluation of injectable enzyme-crosslinked emodin liposome nanohydrogel: Mechanistic study on inhibiting pyroptosis for the treatment of rheumatoid arthritis - Liangwei Wang; Zhongpan Li; Zhilang Xie; Xianghan Hou; Rongzhu Li; Yulin Xiang; Xiaohui Chen; Fulan Zhao; Jiaqi Wu; Guoyou Wang; Rui Huang (Chemical Engineering Journal, 2026)

Less is more: Retaining uncyclized o-quinone group in quinone/pyrazine hybrid molecules for high-energy zinc–organic batteries - Han Yan; Rui Wang; Jinyin Yu; Xiaotang Gan; Housheng Gong; Qian Wang; Zewen Zhu; Xiang Tang; Zhiping Song (Chemical Engineering Journal, 2026)

Multi-level design of a chitosan-based membrane: from sisal fiber reinforcement to surface micropatterning and hybrid hap for enhanced bone regeneration - Shuo Tang; Rui Lin; Yuqing Wang; Xinyuan Feng; Fang Shi; Yupeng Guo; Shu Huang; Xiang Hu; Liuyun Jiang (Carbohydrate Polymers, 2026)

Spatial and environmental niche differentiation facilitates sympatric macaques' coexistence in montane-canyon landscapes: Implications for conservation - Wei Zhou; Yuan Wang; Deyan Ge; Qisen Yang; Gang Song; Jilong Cheng; Tian Tian; Yu Zhang; Jinbo Xu; Ying Liu; Weibo Wang; Xiaochuan Wang; et al. (Biological Conservation, 2026)

Genome-wide association analysis and candidate gene identification for plant height in Shanxi local foxtail millet varieties - Wei Zhou; Huibin Qin; Haigang Wang; Hui Zhi; Rui Huang; Sen Hou; Junjie Wang; Ling Chen; Xiang Tian; Zhijun Qiao; Zhixin Mu; Xianmin Diao (Theoretical and Applied Genetics, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

Ascosphaera apis invasion alters the expression pattern, alternative splicing and alternative polyadenylation of transcripts in the eastern honeybee larval gut - Jianfeng Qiu; Fangji Wang; Xiang Li; Tao Wu; Xin Jing; Zhenzhen Zuo; Jing Tian; Dafu Chen; Rui Guo (Journal of Invertebrate Pathology, 2026)

Centralized mechanical e-waste dismantling is associated with lower farmland soil heavy metal pollution and carbon emission intensity - Yu Zhang; Ming-jiang He; Wei-jun Fu; Jie Wang; Ke-li Zhao; Xiang-rui Xu; Ji-zi Wu (Journal of Environmental Chemical Engineering, 2026)

The fate of exogenous organic matter on ferrihydrite: Critical controls of saturation on carbon and nitrogen sequestration - Fei Chen; Yichen Wu; Leyun Wang; Mengting Zhu; Rui Liu; Xiang Liu; Guanghe Li; Miao Li (Journal of Environmental Management, 2026)

One-step hydrothermal synthesis of Sm-doped BiOIO3 for enhanced photocatalytic removal of mercury from flue gas - Yixuan Shen; Zijian Xiang; Jiang Wu; Sheng Wang; rui Zhu; Yaji Huang; Shaohua Liang; Jingxin Xu; Xueli Sun; Xiuyong Zhao (Fuel, 2026)

Secondhand and thirdhand smoke exposure and the risk of liver cancer: a prospective cohort study of 315,833 Chinese never smokers - Zhi Li; Ling-Xiang Xu; Chun-Rui Wang; Zhang-You Guo; Chen-Wei Tang; Xin Dai; Guo-Chao Zhong (Environmental Pollution, 2026)

Transdermal delivery of small zwitterionic amorphous solid dispersion to increase solubility and penetrate the stratum corneum for psoriasis therapy - Xiang Zhou; Jiahui Ma; Lanlan Wang; Dongyu Zhang; Dongyue Ding; Rui Xu; Ke Wang; Junlong Qi; Yinan Zhong; Dechun Huang; Wei Chen (Chemical Engineering Journal, 2026)

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

MicroRNA-132 Alleviates Ischemia-Reperfusion-Induced Neuronal Apoptosis by Targeting Mecp2 in Stroke Models - Xiang Wang; Rui Ma; Zilu Liu; Wenjin Sun; Lin Xia; Yurou Wang; Donghua Shao; Caixia Sun (Neurotoxicity Research, 2026)

DICP1-A precisely degrades STING-A but not STING-B to suppress IFN expression through the autophagic pathway in gibel carp - Yue Wu; Shun Li; Fan-Xiang Gao; Zhi Li; Rui-Hai Gan; Can Zhang; Xiao-Li Yang; Zhuo-Cong Li; Chu-Jing Zhou; Yang-Yang Wang; Na Xu; Xue-Bing Wang; et al. (Aquaculture, 2026)

Study on the effects of gestational arsenic exposure on the developmental toxicity of brain tissue in mice offspring using network toxicology and RNA-seq - Zitong Wang; Wenjin Qiao; Ruigang Liu; Yuan Lv; Binjie Niu; Tianxu Li; Mengling Zhang; Yanhui Xiang; Rui Qiao; Dapeng Tai (Food and Chemical Toxicology, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

Fabrication of phosphorus@carbon nanotube/Ti4O7 composite anode for enhanced electrochemical degradation of norfloxacin: Nonmetal doping strategies and associated mechanisms - Pingzhou Duan; Haiyang Wang; Rui Pang; Chuanyu Zhang; Lixia Zheng; Yifei Zhang; Li Liu; Xiang Hu; Jian Wei (Chemical Engineering Journal, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

Diosmetin, an active ingredient of Schizonepeta tenuifolia, alleviates acne by regulating inflammation and oxidative stress - Yu Pan; Rui Sun; Elizabeth Rosalind Thomas; Shi Pan; Linli Yang; Wenjun Wang; Lin Chen; Xiang Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Metabolomic changes following PMSG-induced estrus synchronization in Qianbei Ma goats - Feng-Xin Qiao; Yong-Hong Ju; Xiao-Dong Wang; Peng-Cheng An; Quan Ji; Rui-Yang Li; Ting-Ji Zeng; Qing Liu; Dai-Yue Zhang; Zu-Han Feng; Mao-Sheng Cao; Xiang Chen (Animal Reproduction Science, 2026)

Hydrothermal-responsive plasmonic aerogel for dynamic 3D hotspot regulation and ultrasensitive SERS detection of dairy products contaminants - Jing-Xiang Wang; Zhi-Gao Xu; Xin-Rui Wang; Yao-Yao Zhang; Ri-Hui Su; Xin-Xin Zhang; Su-Ming Dai; Wei-Wei Zhu; Xue-Cai Tan; Ke-Jing Huang; Jun Yan (Analytica Chimica Acta, 2026)

Unveiling the “Glycolysis-Lactate-Lactylation” Axis: A Novel Target in Ischemic Cerebrovascular Disease - Yi Xie; Mengmeng Dai; Rui Liu; Ying Li; Hao Yan; Jiacheng Li; Xuantong Liu; Zhiyuan Yu; Shabei Xu; Wei Wang; Xiang Luo (Neuroscience Bulletin, 2026)
Ischemic cerebrovascular disease involves complex interactions between metabolic reprogramming and epigenetic regulation. Recent studies indicate that enhanced glycolysis and lactate accumulation under hypoxic conditions not only maintain cell viability by supplying energy but also participate in disease regulation through lactylation. Lactylation regulates gene expression, immune polarization, metabolic enzyme activity, and angiogenesis through epigenetic remodeling. In ischemic cerebrovascular disease, lactylation exerts dual roles: on one hand, it can induce neuronal death, exacerbate neuroinflammation, and form a vicious metabolic cycle; on the other hand, it can influence immune cell function and gene expression, thereby exerting neuroprotective effects. Accordingly, targeting lactate metabolism or lactylation-modifying enzymes holds considerable therapeutic potential. Nevertheless, the spatiotemporal regulation, synergistic effects, and broader physiopathological implications of lactylation warrant further in-depth investigation. This review systematically summarizes the role of the “glycolysis-lactate-lactylation” axis in the pathogenesis of ischemic cerebrovascular disease, and discusses its potential as a therapeutic target.

Six-component load reconstruction for offshore wind turbine blades considering deformation-induced additional moments - Baoxuan Wang; Xu Liang; Lizhong Wang; Fangyuan Sheng; Xiang Wang; Yue Chen; Jianwei Zhang; Shengjie Rui; Rui Liu (Ocean Engineering, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Millennial-scale hydroclimate variability of the Asian monsoon during MIS 9 from stalagmite records - Sinan Wang; Xunlin Yang; Hai Cheng; Wenming Zhou; Guofeng Li; Wanli Xiang; Rui Zhang; R. Lawrence Edwards (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Recent progress and strategic perspectives of Na3V2(PO4)2F3 cathode: mechanisms, syntheses, and modifications in zinc-ion batteries - Rui Jiang; Jiajie Zhou; Sheng Ouyang; Xiaoyan Shi; Junling Xu; Xiang Wang; Lianyi Shao; Zhipeng Sun (Next Research, 2026)

Pseudo-static test and numerical study of beam-column joints with novel replaceable energy-dissipating shear disc - Kaihang Zhang; Xiang Zhu; Rui Wang; Qing Jiang; Guangze Lei (Engineering Structures, 2026)

Dual-phase Co/CoFe nanoparticles anchored on N, F co-doped hollow carbon microcapsules as efficient bifunctional catalysts for aqueous/quasi-solid-state Zn-air batteries - Bin Cui; Yunfeng Zhu; Xingyue Fang; Renjing Du; Jiabao Bai; Mengran Li; Wanting Xiang; Wenxuan Xie; Yana Liu; Jiguang Zhang; Rui Shi; Jun Wang; et al. (Chemical Engineering Journal, 2026)

An earthworm-inspired hydrogel coating for hydration-assisted aqueous lubrication on diverse polymer substrates - Zhi-Guo Wang; Xi Liao; Yong-Jie Dan; Yu-Wei Liu; Yan-Hua Niu; Rui Hong; Ming Cai; Ju-Xiang Gou; Jia-Zhuang Xu; Zhong-Ming Li; Ka Li (Chemical Engineering Journal, 2026)

Revealing ozone persistence under typhoon subsidence in the Greater Bay Area using lidar observations - Rui He; Zhongcai Wang; Yongfan Wu; Yan You; Yan Xiang; Andi Zhang; Chenglei Pei; Tianshu Zhang (Atmospheric Research, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Precambrian crustal evolution of the southern margin of the North China Craton: Evidence from the Paleo–Mesoproterozoic sedimentary rock - Shuo Wang; De-Bin Yang; Xiang-Yu Yan; Ke Wu; Jian-Ning Liu; Rui-Qing Xue (Journal of Asian Earth Sciences, 2026)

Enhancing the catalytic performance of ZnZrOx/SAPO-34 bifunctional catalysts through structural modulation - Rui Xiang; Tao Du; He Jia; Yingnan Li; Peng Chen; Qiang Yue; Heming Wang; Yisong Wang (Journal of Environmental Chemical Engineering, 2026)

Investigation on the deodorization effect and mechanism of deodorant-rubber asphalt - Hui Wang; Tao Chen; Huiyun Wu; Junwei Xiang; Yujie Huang; Shuihui Wu; Juan Xie; Pu Zhao; Weiyong Rui (Fuel, 2026)

Mechanism of Chain Rockbursts in Deep Excavations Triggered by Dynamic Disturbance: Insights from Stress Path Controlled Failure - Biao Wang; Ben-Guo He; Xiang-Rui Meng; Hong-Pu Li; Zhao-Tong Jin (Rock Mechanics and Rock Engineering, 2026)

Genome-wide identification of TGA transcription factors in wheat and the TaTGA13 negatively modulates stripe rust resistance - Jiajie Liu; Rui Li; Mingjie Xiang; Xunyin Yuan; Yifan Tian; Xuanqi Zhang; Jingyao Wang; Jianhui Wu; Qingdong Zeng; Dejun Han (Plant Science, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Enhanced evapotranspiration prediction by incorporating plant stomatal-hydraulic co-regulation into hydrological model - Yong Liu; Tiesong Hu; Huandi Li; Xiang Zeng; Rui Zhu; Peiran Jing; Qifan Zhang; Xiang Li; Yanxuan Wang (Journal of Hydrology, 2026)

Iron-driven synergism among microbial functional taxa facilitates recovery from denitrification toxicity - Yongzhi Zhang; Xiaoxiao Li; Linjun Gao; Ping Ye; Rui Wang; En Zhou; Tian Sun; Miaoqing Xu; Rui Wan; Xiang Li (Journal of Environmental Management, 2026)

Efficient oxygen evolution in acidic electrolysis of water using copper loaded with iridium nanoclusters - Yanan Song; Bingxin Zhang; Tai Xiang; Huabin Wang; Yong Zhang; Xiaoning Tang; Lin Tian; Rui Xu (Journal of Environmental Sciences, 2026)

Nitrogen sites induce homogeneous dispersion of iron species on biochar for enhanced hydrogen sulfide removal in a low-temperature anaerobic environment - Jiayu Feng; Fei Zhao; Huang Xiang; Fang Wang; Shuo Cui; Zibin Pan; Rui Cao; Ping Ning; Lijuan Jia (Bioresource Technology, 2026)

Efficient bioconversion of corn stover hydrolysates into phenazine-1-carboxylic acid by engineered Pseudomonas chlororaphis for sustainable biopesticide production - Sheng-Jie Yue; Yu-Xuan Li; Kai-Quan Liu; Sheng-Xiao Zhang; Peng Huang; Wei Wang; Xue-Hong Zhang; Xiang-Rui Hao; Lian Jiang; Hong-Bo Hu (Bioresource Technology, 2026)

Reconstruction of high-precision gridded precipitation dataset in the alpine cold regions of the Qilian Mountains: An intelligent technological framework from downscaling to calibration - Renjun Wang; Xiang Qin; Yushuo Liu; Jianyu Zhao; Rui Zhang; Zizhen Jin; Yanzhao Li; Wentao Du; Jizu Chen; Weijun Sun (Atmospheric Research, 2026)

Screening of Fecal Bacteroides Strains and Discovery of Bacteroides eggerthii S13-F8 with Protective Effects Against Chemotherapy-Induced Diarrhea - Yi Zhao; Zhengqun Dai; Yanmei Lang; Rui Li; Hongyu Zheng; Jiajia Mi; Xiu He; Jin Liu; Rong Xiang; Xueran Mei; Yang Liu; Yantang Wang; et al. (Probiotics and Antimicrobial Proteins, 2026)

A near-infrared hemicyanine-derived fluorescent probe for sulfite detection in biomedical investigate - Kai Wang; Dan-Xian Cai; Hao-Xiang Jiang; Zi-Rui Luo; Hong-Rui Zhan (Analytica Chimica Acta, 2026)

Precise construction of Anderson-type polyoxometalate-based covalent organic frameworks for photocatalytic hydrogen peroxide production - Zhang-Di Liu; Zai-Xiang Zhang; Yang Yang; Rui Xing; Zi-Hao Wei; Hou-He Liu; Jiang-Bo Ming; Jin Zhu; De-Yin Wang (Journal of Water Process Engineering, 2025)

Discriminating nanoparticulate and ionic silver in vivo: Organ-specific distribution and toxicological outcomes via gold-core labeling - Xiang-Rui Wang; Dingyuan Liang; Xiaoli Zhao; Ying Wang; Wen-Hong Fan (Journal of Hazardous Materials, 2025)

PMTFIM: Integrating machine learning with nutrient balance theory to estimate multi-stage paddy fertilization information at field scale over large regions - Housheng Wang; Xiang Gao; Wei Jiang; Xuerong Lang; Xian Hu; Meihua Qiu; Qiankun Guo; Yonghong Liang; Xuelei Wang; Yue Mu; Rui Ren; Ganghua Li; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Bioinspired mortise-tenon interlocking HKUST-1/CuOH micro-nano architectures on stainless steel mesh for oil-water separation membranes - Xiang Li; Ping Zhang; Rui Wang; Meng Zhu; Xiaobo Gong; Yucheng Liu (Environmental Research, 2025)

Synergistic lattice engineering and surface passivation via cerium modification for robust ultrahigh-nickel layered oxide cathodes - Lunhao Deng; Rui Zhou; Jie Chen; Xiaotian Xu; Yuanyuan Chen; Xinyu Zhao; Liang Luo; Wang Xiang; Xiangwan Lai; Yingjie Zhang; Xianshu Wang; Ding Wang; et al. (Chemical Engineering Journal, 2025)

A single chitosan-based fluorescent sensor for the discriminant analysis and quantitative detection of bisulfite and oxytetracycline in real samples - Chao Gao; Rui-Xue Li; Xiang Li; Zhenxing Zhong; Jia-Hui Wang; Wei Li (Carbohydrate Polymers, 2025)

Correction: Combining network Pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Combining network pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Temporal transcriptomics reveal crucial networks underlying jasmonate-mediated diurnal floret opening and closure in rice - Rui Zhang; Xiaohui Xi; Xiaozhou Hu; Dan Xiang; Yi Wang; Yu Pan; Xi He; Yuhan Zhang; Lilan Hong; Yuanzhu Yang; Ming Zhou (Science China Life Sciences, 2025)

Multi-omics based consensus subtypes, development of prognostic signature, and identification of INHBB as a potential therapeutic target in colorectal cancer - Xu Wang; Yuanmin Xu; Rui Sun; Sheng Wang; Xiang Wei (Functional & Integrative Genomics, 2025)

Electronic tuning of MoS2 nanosheets by Ag atoms doping for efficient hydrogen evolution reaction - Xiang Liu; Hongjie Zhu; Rui Lu; Hongsen Wei; Huijie Sun; Yumo Wang; Ailing Zhang; Kexin Lv; Lei Zhang; Haibin Zhang; Hengcheng Wan (Process Safety and Environmental Protection, 2025)

Deep learning approach for internal tide prediction based on China Ocean Reanalysis data - Rui Su; Jun Zhao; Senliang Bao; Hongli Fu; Huizan Wang; Xiaojiang Zhang; Xiang Wang; Can Ma; Weimin Zhang; Xinrong Wu (Ocean Engineering, 2025)

Study on the distribution characteristics and toxic risks of trace elements in the eggs of green turtles (Chelonia mydas) nesting on the Xisha Islands - Xiang Li; Li Jian; Minyu Fu; Henyi Zhang; Yuxin Zhang; Rui Guo; Jichao Wang (Environmental Research, 2025)

Fusarium infection alters the effects of vegetable residue and its compost on nitrous oxide emissions from acid soil - Yumeng Xu; Xiaoxiao Xiang; Waqar Ahmed; Junhui Yin; Owen Fenton; Wenxuan Shi; Jiaqi Wang; Ruixue Chang; Rui Liu; Hao Chen; Guorong Xin; Qing Chen (Applied Soil Ecology, 2025)

Dihydromyricetin switches pyroptosis to apoptosis during Aeromonas hydrophila infection in Mylopharyngodon piceus - Jingjing Xu; Can Yang; Jing Xiang; Rui Song; Dongsheng Ou; Ruozhong Wang (Fish & Shellfish Immunology, 2025)

Sunlight-activated photochromic-photothermal nanofibrous textiles for self-monitored thermal management - Shuai Liang; An-Yang Duan; Shi-Kun Yan; Yan-Rui Zhao; Jin Zhang; Guo-Wei Xiao; Chang-Hai Xu; Ji-Xiang Hu; Guo-Ming Wang (Chemical Engineering Journal, 2025)

Selective adsorptive separation of xylene isomers in vapor and liquid phases by nonporous adaptive crystals of leaning pillar[6]arenes - Yu-Xiang Sun; Susu Ren; Gengxin Wu; Xiang-Shuai Li; Haitao Wang; Jia-Rui Wu (Chemical Engineering Journal, 2025)

Impacts of green manure rotations and alkaline amendments on soil health and assembly and function of bacterial communities - Jinchang Liang; Heli Shi; Bikun Xiang; Luping Chi; Rui Wang; Guangwei Sun; Yuxiao Sun; Jing Wang; Jun Tan; Xiaoqiang Wang (Applied Soil Ecology, 2025)

High-performance prediction of soil organic carbon using automatic hyperparameter optimization method in the yellow river delta of China - Yingqiang Song; Feng Wang; Weihao Yang; Ruilin Liang; Dexi Zhan; Meiyan Xiang; Xiaohang Yang; Rui Xu; Miao Lu (Computers and Electronics in Agriculture, 2025)

Enhancing the participation of water in the anaerobic digestion of sewage sludge for highly efficient methanogenesis - Jiachang Cao; Ying Xu; Chen Zhang; Xiang Li; Rui Liu; Xueye Wang; Xiaohu Dai (Water Research, 2025)

Ionic liquid modified MOF-808 for efficient adsorption and stable capture of radioactive iodine - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Wen-Rui Zhang; Xiang-Hua Qi; Chun-Hui Gong; Peng Wang; Man-Li He; Yi Yang (Journal of Environmental Management, 2025)

Construction of double S-scheme heterojunction in MIL-125(Ti)/ZnIn2S4/ZnS QDs to improve interfacial charge transfer and reduction potential for photocatalytic hydrogen production - Xiuxiu Huang; Shijian Zhang; Wenbin Ruan; Xinru Wang; Xiang Li; Shuangshuang Huai; Rui Cheng; Congliang Cheng; Ping Li; Jingjing Xia; Xiufang Wang (Fuel, 2025)

Enhancing flame retardancy and mechanical properties of epoxy/carbon fiber composites via a metal-phosphorus synergistic interface structure - Dou Hu; Guo-rui Zhang; Xiao-dong Qi; Jing-hui Yang; De-xiang Sun; Yong Wang (Chemical Engineering Journal, 2025)

A Co(III)-dipyrazolate framework for atmospheric CO2 photoreduction - Yingjie Wang; Xiang-Jing Kong; Guang-Rui Si; Tao He; Da-Yu Chen; Jian-Yu Zhang; Na Xing; A-Wu Zhou; Jian-Rong Li (Chemical Engineering Journal, 2025)

A rapid and efficient microenvironment improving hyaluronic acid microneedle dressing for burn wound synergistic treatment - Lin Lei; Wei Li; Jiajia Wang; Qi Liu; Feng Zeng; Yunqiang Xiang; Xinyuan Fu; Rui Tao; Zhangyou Yang (Carbohydrate Polymers, 2025)

Uncovering the transcriptional regulatory network underlying selenium tolerance in maize seedlings - Rui Wang; Hualei Zhang; Zihan Liu; Yingao Lu; Shouxin Lan; Bin Zhang; Shuai Li; Qian Li; Jingyu Ma; Xiaoli Xiang; Changsheng Li (Journal of Hazardous Materials, 2025)

Iron valence regulates sulfur pollution in livestock manure compost: A multipath strategy of chemical fixation-oxidation and microbial metabolism - Qi Wu; Wenfang Gao; Xu Wang; Rui Sun; Yanjie Jiao; Xiang Li; Zimin Wei (Chemical Engineering Journal, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Substrate type-driven differences in interfacial microbial community and pathogenic risk: Clay, microplastics and activated carbon - Taishuo Zhang; Wenfu Wang; Xiang Zhi; Xiaoqian Ye; Rui Wang; Jiarui Zhao; Jiamin Dai; Hong Qiang; Peng Liu; Hanzhong Jia (Gondwana Research, 2025)

Assessing the potential for a novel Composite Integrative Passive Sampler (CIPS) to investigate transboundary movement of organic chemicals in the Tijuana River Estuary - Zuying Feng; Flannery McLamb; Damian Shea; Kesten Bozinovic; Chris Stransky; Richard M. Gersberg; Wenling Wang; Xiang Kong; Xin-Rui Xia; Miguel F. Vasquez; MacKenzie King; Goran Bozinovic (Science of The Total Environment, 2025)

Ligand-rich oxygen evolution electrocatalysts reconstructed from metal-organic frameworks for anion-exchange membrane water electrolysis - Shiqi Li; Weiwei Liu; Yi Shi; Tang Wang; Tianyang Liu; Xiang Xue; Rui Li; Man Qiao; Zhen-Yu Wu; Wang Zhang (Science Bulletin, 2025)

Enhancing regional-scale simulation accuracy of paddy runoff by coupling water balance models with remote sensing - Housheng Wang; Rui Ren; Xiang Gao; Huazhan Zhang; Wei Jiang; Xuerong Lang; Xian Hu; Xiaosan Jiang; Kun Zhao; Bin Zhang; Zhipeng Liu; Wenjuan Zheng; et al. (Journal of Hydrology, 2025)

Study on the flame retarding mechanism of HFC-134a on hydrocarbon refrigerants - Rui Zhai; Xiang Li; Yuan Zhuang; Bin Ye; Xiangnong Liu; Qingqing Li; Lei Tang; Ke Wang (International Journal of Refrigeration, 2025)

Development of cascade nanoreactors by fusing bone-targeting engineered extracellular vesicles to modulate bone microenvironment for treatment of diabetic osteoporosis - He Yi; Fang Depeng; Chen Xiang; Shen Hongdou; Shao Xiaoyan; Lin Jiaquan; Liu Na; Shen Tao; Wang Chengzhi; Zhang Pan; Peng Rui; Mu Jinglan; et al. (Chemical Engineering Journal, 2025)

Heavy-Duty Diesel Trucks on Highways in Beijing-Tianjin-Hebei: Constant Challenge in Pollution Control - Yingying Han; Chang Wang; Yixue Zhu; Rui Wu; Yifeng Xue; Xiang Zhang; Weiwei Wang; Yangyang Cui; Jinxiu Han; Zongbo Shi; Xiuyan Wang; Taosheng Jin (Water, Air, & Soil Pollution, 2025)

The mouse resource at National Resource Center for Mutant Mice of China - Bingzhou Han; Dongshen Chen; Zhong Chen; Ting Wang; Kaiyuan Zi; Rui Feng; Xiaoliu Yang; Ling’en Li; Juan Liang; Xiang Gao (Mammalian Genome, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Tracking of single virus: Dual fluorescent labeling of pseudorabies virus for observing entry and replication in the N2a cells - Mingzhi Li; Li Pan; Caoyuan Ma; Hongxia Wu; Guangtao Xiang; Lian-Feng Li; Tao Wang; Rui Luo; Yongfeng Li; Di Liu; Huanjie Zhai; Moon Assad; et al. (Veterinary Microbiology, 2025)

L-arginine-enhanced PEI-based polyamide Nanofiltration membranes for efficient heavy metal ion removal - Junwei Li; Shan Wang; Qingjuan Zhu; Daliang Xu; Yongmei Wang; Xi Zhang; Jiale Du; Qin Chen; Rui Zhao; Xiang Hu; Yong Liu; Raf Dewil; et al. (Desalination, 2025)

Cardiovascular dysfunction and altered lysosomal signaling in a murine model of acid sphingomyelinase deficiency - Yun-Ting Wang; Alexandra K. Moura; Rui Zuo; Kiana Roudbari; Jenny Z. Hu; Saher A. Khan; Zhengchao Wang; Yangping Shentu; Mi Wang; Pin-Lan Li; Jiukuan Hao; Yang Zhang; et al. (Journal of Molecular Medicine, 2025)

Applicability analysis of passive containment heat remove system calculation model based on integrated code - Nan Zhang; Shuai Yuan; Xiang Xia; Chang Wang; Rui Hao (Annals of Nuclear Energy, 2025)

Undrained permanent deformation characteristics of Yellow River silt under one-way cyclic loads - Yuke Wang; Hao Chen; Yujie Xue; Rui Jiang; Xiang Yu; Xiaoying Lin (Marine Georesources & Geotechnology, 2025)

Variability in maternal transfer efficiency of trace elements in green turtles (Chelonia mydas) - Li Jian; Xiang Li; Xiaobo Zheng; Henyi Zhang; Minyu Fu; Rui Guo; Jichao Wang (Environmental Pollution, 2025)

A magnetic nanoreactor with microenvironment regulation capability for targeted and enhanced tumor chemodynamic therapy - Xia-Nan Li; Qin-Ying Tang; Meng-Cheng Tang; Hai-Rui Deng; Kang Hu; Ling-Feng Pan; Shi-Bo Wang; Bin Li; Xiang-Dong Kong (Chemical Engineering Journal, 2025)

Unraveling Neurotoxicity Discrepancies: Comparative In vitro and In vivo Analysis of Colistin and Polymyxin B and the Underlying Mechanisms - Rui Yang; Debiao Xiang; Fang Yuan; Yuan Yang; Pengkai Wang; Bing Xu; Xin Li (Molecular Neurobiology, 2025)

Streptomyces adonidis sp. nov., a novel actinomycete strain with antifungal activity isolated from the root of Adonis amurensis Regel - Rui Du; Hui Bing; Wentian Lu; Congting Gao; Fanxue Kong; Hongtu Wang; Yue Shen; Chongxi Liu; Wensheng Xiang (Antonie van Leeuwenhoek, 2025)

Novel approaches for alleviating shallow soil compaction using microbial fertilizers and their beneficial impacts on plant growth and soil physicochemical properties - Xiang Yao; Hailin Guo; Dandan Li; Junqin Zong; Rui Zhang; Jingbo Chen; Dongli Hao; Xinyong Zhao; Jianxiu Liu; Haoran Wang; Chunjie Li (Soil and Tillage Research, 2025)

Sulfur dioxide increases testosterone biosynthesis by activating ERK1/2 pathway and disrupting autophagy in Leydig cells - Xiang Li; Yan Shi; Sha Liu; Zhiyuan Feng; Haoran Xiao; Rui Li; Zirou Li; Xinyue Zhang; Yongli Han; Jundong Wang; Chen Liang; Jian Bai; et al. (Journal of Hazardous Materials, 2025)

Ultrasound-assisted extraction of flavonoids from Rudbeckia hirta L. flowers using deep eutectic solvents: Optimization, HPLC analysis and anti-inflammatory activity - Jiang-Rui Wang; Yin-Long Li; Hai-Tao Zhang; Zhao-Bao Xiang; Jing Zuo; Bo Peng; Xing-Yu Liu; Hong Ou (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Analysis of the city-scale wind environment and detection of ventilation corridors in high-density metropolitan areas based on CFD method - Rui Liu; Yuxiang Wang; Yu Zhang; Zhixing Peng; Hankai Chen; Xiang Li; Hang Li; Weiyue Li (Urban Climate, 2025)

Human cardiac organoid model reveals antibacterial triclocarban promotes myocardial hypertrophy by interfering with endothelial cell metabolism - Nana Yang; Jiahong Chen; Yujie Zhu; Wenxin Shan; Zheng Cao; Yiwen Fu; Huanhuan Cao; Yanyan Li; Yukun Xiang; Shusi Ding; Huiqing Wang; Yaobo Zhao; et al. (Science Bulletin, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Molecular disturbances and thyroid gland dysfunction in rats chronically exposed to a high dose of NaAsO₂: Insights from proteomic and phosphoproteomic analyses - Jie Xiang; Lili Fan; Hui Li; Qian Song; Ying Jin; Rui He; Xueli Pan; Dapeng Wang (Journal of Hazardous Materials, 2025)

Regulation of multilayer long crystalline MoS2 by NiO-modified Al2O3 for improved hydrodesulfurization of COS - Yubiao Li; Yu Liu; Xueqian Wang; Yixing Ma; Ping Ning; Langlang Wang; Xiang Li; Rui Cao (Environmental Research, 2025)

Synchronous monitoring agricultural water qualities and greenhouse gas emissions based on low-cost Internet of Things and intelligent algorithms - Huazhan Zhang; Rui Ren; Xiang Gao; Housheng Wang; Wei Jiang; Xiaosan Jiang; Zhaofu Li; Jianjun Pan; Jinyang Wang; Songhan Wang; Yanfeng Ding; Yue Mu; et al. (Water Research, 2025)

Heat-resistant boron Carbonitride with nitrogen-vacancies and oxygen-doping for efficient tetracycline removal: Adsorption characteristics, mechanism and regeneration - Xu-Dong Miao; Rui-Xiang Zhang; Wen-Tao Li; Qian Wang; Yu-Han Cai; Yong Guo; Ai-Min Li (Journal of Water Process Engineering, 2025)

U-shaped relationship between environmental regulation and the digital transformation of the Chinese coal industry: Mechanism and moderating effects - Pu-hao Guo; Xiang-qian Wang; Xiang-rui Meng (Journal of Environmental Management, 2025)

In-situ experiments of dynamic microscopic reaction for CO2-brine-carbonate system - Yulong Zhao; Yongchao Wang; Shaomu Wen; Liehui Zhang; Zhenglin Cao; Zihan Zhao; Wei Xiong; Cheng Cao; Rui Tang; Yunting Fan; Zehao Xie; Ruihan Zhang; et al. (Chemical Engineering Journal, 2025)

Construction risk probability assessment of shield tunneling projects in karst areas based on improved two-dimensional cloud model - Huaiyuan Sun; Yi Rui; Yanyun Lu; Yiming Dai; Xiang Wang; Xiaojun Li (Tunnelling and Underground Space Technology, 2024)

Spatial and temporal evolution and factors influencing soil aggregate stability in the riparian zone during exposure: A case study of the water-level fluctuation zone of the Three Gorges Reservoir, China - Yuanzhen Ni; Zhenyao Xia; Yueshu Yang; Deyu Liu; Rui Xiang; Yu Ding; Huan Hong; Di Wang; Hai Xiao (Science of The Total Environment, 2024)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Reduced phytoplankton biomass in a subtropical plume-upwelling system induced by typhoons Bailu and Podul - Zhuyin Tong; Lingqi Ma; Shujie Cai; Zhaoyun Chen; Lei Wang; Mingwang Xiang; Rui Huang; Meilin Wu; Wupeng Xiao; Bangqin Huang (Progress in Oceanography, 2024)

Transcription combined metabolic analysis reveals the mechanism of potassium phosphate enhances resistance to walnut anthracnose (Colletotrichum gloeosporioides) - Guifang Wang; Yuantao Yao; Haifeng Xu; Kun Xiang; Meiyong Zhang; Junpei Zhang; Rui Zhang; Xin Chen (Postharvest Biology and Technology, 2024)

Recovery of low-concentration waste acid by electrodialysis: Modeling and validation - Feng-rui Li; Yu-xiang Jia; Meng Wang (Journal of Cleaner Production, 2024)

Protective mechanism of antioxidant peptides derived from dry-cured ham against ultraviolet A-induced oxidative damage in HaCat cells - Rui-hong Xie; Shan Xiao; Da Ma; Bo Wang; Guan-chao Chen; Jun-han Xiang; Ji-hui Wang (Food Bioscience, 2024)

Curcumin protects porcine granulosa cells and mouse ovary against reproductive toxicity of aflatoxin B1 via PI3K/AKT signaling pathway - Sihong Li; Rui Li; Jun Jiang; Lu Liu; Xiang Ma; Tao Wang; Lili Zhao; Weifen Li; Dong Niu (Environmental Pollution, 2024)

Deciphering the nonlinear and synergistic role of building energy variables in shaping carbon emissions: A LightGBM- SHAP framework in office buildings - Congyue Zhou; Zhu Wang; Xuanli Wang; Rui Guo; Zhao Zhang; Xingwei Xiang; Yiqun Wu (Building and Environment, 2024)

Chang’E-7 Lunar Soil Water Molecule Analyzer (LSWMA) Prototype for High-Precision Measurement of Water Content and Hydrogen Isotope Ratio - Rui Chen; Wenzhen Lu; Xiang Li; Xingping Wang; Kan Chen; Chi Zhang; Nailiang Cao; Zhenyu Xu; Yi Xu; Ruifeng Kan; Renrui Liu; Qiquan Yang; et al. (Journal of Earth Science, 2024)

Berbamine inhibits porcine epidemic diarrhea virus in vitro and in vivo - Hongwei Xiang; Jixue Qiao; Haicheng Lin; Jie Li; Yangfan Li; Huihui Sun; Xuan Wang; Ruimin Bi; Zuyao Zhang; Zongyi Bo; Haixiao Shen; Jinchi Zhou; et al. (Veterinary Microbiology, 2024)

T cell senescence may contribute to immunothrombosis via Th17 immune transition in COVID-19 - Wenxing Li; Rui Qian; Zhaoming Zhou; Lei Wen; Quan Yin; Xiang Zhou; Xiaowei Li; Jie Cheng; Xinlu Zhang; Xin Zeng; Zhuoya Wang; Yingying Huang; et al. (Science Bulletin, 2024)

Myosuppressin signaling deficiency affects ovarian development via repression of 20-hydroxyecdysone biosynthesis in Grapholita molesta - Jie Cheng; Jing-Kai Liu; Tian-Li Wang; Wei Wei; Hui-Ming Xiang; Xian-Wei Li; Rui-Yan Ma; Zhi-Guo Zhao (Pesticide Biochemistry and Physiology, 2024)

Cost-efficient breakthrough: Fabricating multifunctional woven hydrogels from water-soluble polyvinyl alcohol yarn - Chenxing Xiang; Yuanhao Tian; Huiming Ning; Ning Hu; Lidan Zhang; Feng Liu; Rui Zou; Shu Wang; Jie Wen; Leilei Li (Chemical Engineering Journal, 2024)

Phase change thermal interface film with bicontinuous and textured filler network for efficient wearable heat dissipation - Jia-Qing Zhao; Xiang Wang; Xun-Rui Wang; Hong-Wei Zhao; Mei-Na Lu; Wayne-Qiang Xu; Hong-En Nian; Jin-Hong Li (Chemical Engineering Journal, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Smart nanoscale lamellated supramolecular assemblies overcome biofilm barriers and enhance foliar affinity for efficient control of bacterial diseases - Lizhu Xiang; Xiaohui Wang; Jinghan Yang; Rui Wang; Lin Chen; Xiaoping Bao; Xianfu Mu; Peiyi Wang (Chemical Engineering Journal, 2024)

Construction of La/Al2O3 nanorod-like catalyst with rich basic sites: Enabling efficient conversion of COS-superior selectivity and theoretical insights - Rui Cao; Xueqian Wang; Langlang Wang; Fangxian Cao; Xiang Li; Lu Wang; Jinghao Xiang; Ping Ning (Chemical Engineering Journal, 2024)

Hybrid packed bed bioreactor using combined biodegradation and ozonation to enhance nitrogen and micropollutants removal from landfill leachate - Xuetong Yang; Ze Liu; Changtao Chen; Tao Zhang; Qintong Wang; Rui Zhang; Feng Duan; Xiang Tian; Mingshui Yao; Kristof Demeestere; Stijn W.H. Van Hulle (Bioresource Technology, 2024)

Yr29 combined with QYr.nwafu-4BL.3 confers durable resistance to stripe rust in wheat cultivar Jing 411 - Mingjie Xiang; Bo Tian; Jianghao Cao; Shengjie Liu; Caie Zhou; Xiaoting Wang; Yibo Zhang; Jiale Li; Xunying Yuan; Jufen Wan; Rui Yu; Weijun Zheng; et al. (Theoretical and Applied Genetics, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Water pollution control promotes sustainable water use in Yangtze River Economic Belt——from water footprint perspective - Ruining Jia; Zhongwen Yang; Rui Xia; Yan Chen; Lu Wang; Chen Yang; Hui Zhang; Qiang Hu; Xiang Li; Yingze Yin; Nixi Zhong; Chao Yan (Environment, Development and Sustainability, 2024)

Improving energy-related efficiency towards SDG7 in China: What role does energy poverty play? - Lina Zhang; Guilan Xiong; Rui Ni; Yung-ho Chiu; Qinghua Pang; Zhen Shi; Xiang Wang (Journal of Environmental Management, 2024)

Effects of soy protein on alleviating iron deficiency anemia in suckling rats with different iron supplements - Mengxiao Hu; Jun Zhou; Lili Qiu; Rui Song; Xiyu Qin; Zidi Tan; Wei Wang; Rong Liu; Yun Li; Yingyi Mao; Xiang Li; Fei Li; et al. (Food Bioscience, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

Antiviral C-geranylated flavonoids from Artocarpus communis - Rui-Li Huang; Wei Tang; Chaoqun Wang; Cong Yan; Yun Hu; Hai-Xia Yang; Hai-Yang Xiang; Xiao-Jun Huang; Li-Jun Hu; Wen-Cai Ye; Jian-Guo Song; Ying Wang (Phytochemistry, 2024)

Liquidizing crystal MIL-100(Fe) to coating silica powder for purifying wastewater - Shiyong Wei; Aijia Cao; Siyuan Huang; Yao Shen; Ting Lei; Songmei Luo; Mingjun Cai; Wenjun Xiang; Anying Chen; Rui Wang (Chemical Engineering Journal, 2024)

An information quantity and machine learning integrated model for landslide susceptibility mapping in Jiuzhaigou, China - Yunjie Yang; Rui Zhang; Tianyu Wang; Anmengyun Liu; Yi He; Jichao Lv; Xu He; Wenfei Mao; Wei Xiang; Bo Zhang (Natural Hazards, 2024)

Sandwich-structured continuous ZIF-8/Ti3C2 MXene/ZIF-8 for efficient sterilization: Enhanced photocatalytic activity, photothermal effect, and environmental safety - Furong Xiong; Huilin Hu; Xiang Xue; Minqi Wu; Jiajie Zhou; Wang Zhang; Rui Li (Water Research, 2024)

Enhanced photocatalytic U(VI) reduction via double internal electric field in CoWO4/covalent organic frameworks p-n heterojunction - Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Xiao-Xing Wang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

The transport of bismuth in HCl-bearing aqueous vapour and low-density aqueous supercritical fluids: Implications for natural systems - Xin-Song Wang; A.E. Williams-Jones; Rui-Zhong Hu; Qi Liu; Fei-Xiang Liu; Yuan Mei; Zi-Qi Jiang; Lin-Bo Shang; Jing-Jing Zhu; Xian-Wu Bi (Geochimica et Cosmochimica Acta, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Manganese oxides/graphene aerogels as lightweight microwave absorbers for extreme environment application - Jieping Wang; Shaohua Shi; Yongzhu Yan; Gengping Wan; Haoxiang Zhai; Xiang Yuan; Liang Li; Changlong Du; Rui Liu; Guizhen Wang (Chemical Engineering Journal, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

Assessing the ecological security of the Three Gorges reservoir complex ecosystem based on the improved three-dimensional emergy ecological footprint model - Peiran Jing; Jinbao Sheng; Yi Wang; Tiesong Hu; Lidan Guo; Rui Zhu; Kai Dong; Ali Mahmoud; Yong Liu; Xiang Li (Science of The Total Environment, 2024)

Responses of rainfall partitioning to water conditions in Chinese forests - Qi Wu; Rui Yang; Hui Zeng; Xiang Wang; Guo Chen (Journal of Hydrology, 2024)

Experimental study on long-term impermeability of recycled aggregate concrete mixed with crystalline admixture and waste glass powder - Yankai Wang; Xiang Fan; Rui Wu; Hang Lin; Wenwen Feng (Journal of Cleaner Production, 2024)

Epidemiology, pathogenesis, immune evasion mechanism and vaccine development of porcine Deltacoronavirus - Xueting Shan; Rui Li; Xiang Ma; Guoqiang Qiu; Yi Xiang; Xiaojun Zhang; De Wu; Lu Wang; Jianhong Zhang; Tao Wang; Weifen Li; Yun Xiang; et al. (Functional & Integrative Genomics, 2024)

Weakened hydrological oscillation period increased the frequency of river algal blooms - Qiang HU; Yan CHEN; Rui XIA; Xiaoyu LIU; Ruining JIA; Kai ZHANG; Xiaoxuan LI; Chao YAN; Yao WANG; Yingze YIN; Xiang LI; Junde MING (Water Research, 2024)

Slope Stability Analysis under Heavy Rainfall Conditions Based on a Modified Green-Ampt Model - Yunxin Zheng; Zhiping Hu; Rui Wang; Xin Wen; Xiang Ren; Rui Pan (Water Resources Management, 2024)

Metagenomic insights into the toxicity of carbamazepine to functional microorganisms in sludge anaerobic digestion - Yinping Xiang; Weiping Xiong; Zhaohui Yang; Rui Xu; Yanru Zhang; Mengru Wu; Yuhang Ye; Haihao Peng; Weimin Sun; Dongbo Wang (Science of The Total Environment, 2024)

Core-shell MOF@COF photocatalysts for synergistic enhanced U(VI) and tetracycline cleanup through space and carrier separation - Rui-Xiang Bi; Xin Liu; Lan Lei; Zhi-Hai Peng; Xiao-Xing Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Modulator of TMB-associated immune infiltration (MOTIF) predicts immunotherapy response and guides combination therapy - Zheng-Yu Qian; Yi-Qian Pan; Xue-Xin Li; Yan-Xing Chen; Hao-Xiang Wu; Ze-Xian Liu; Martin Kosar; Jiri Bartek; Zi-Xian Wang; Rui-Hua Xu (Science Bulletin, 2024)

A high-affinity fluorescent probe for human uridine-disphosphate glucuronosyltransferase 1A9 function monitoring under environmental pollutant exposure - Yi-Sheng Miao; Jia-Yue Wang; Rui-Rui Zhuang; Xiao-Kui Huo; Zi-Chang Yi; Xiao-Nan Sun; Zhen-Long Yu; Xiang-Ge Tian; Jing Ning; Lei Feng; Xiao-Chi Ma; Xia Lv (Journal of Hazardous Materials, 2024)

Quantitative health risk assessment of microbial hazards from water sources for community and self-supply drinking water systems - Cheng Yan; Wei-di Wan; Rui-ning Wang; Tian-nuo Lai; Wajid Ali; Shan-shan He; Sai Liu; Xiang Li; Zaheer Ahmad Nasir; Frederic Coulon (Journal of Hazardous Materials, 2024)

Factors affecting chemical and textural properties of dried tuber, fruit and vegetable - Yue Li; Han Zhao; Kexin Xiang; Dajing Li; Chunju Liu; Haiou Wang; Wenqian Pang; Liying Niu; Rui Yu; Xiyun Sun (Journal of Food Engineering, 2024)

Dietary gallic acid as an antioxidant: A review of its food industry applications, health benefits, bioavailability, nano-delivery systems, and drug interactions - Zedong Xiang; Huida Guan; Xiang Zhao; Qi Xie; Zhejun Xie; Fujie Cai; Rui Dang; Manlin Li; Changhong Wang (Food Research International, 2024)

Boric acids decorated polymers with Au nanoparticle anchor assisted laser desorption/ionization for qualitive and quantitative analysis of hydroxytyrosol in red wines - Xiaohui Huang; Baichun Wang; Rui Zhai; Chuan-Fan Ding; Xiang Fang; Xinhua Dai; Yinghua Yan (Food Chemistry, 2024)

Soil nutrients drive changes in the structure and functions of soil bacterial communities in a restored forest soil chronosequence - Rui Guo; Yiyue Chen; Meiren Xiang; Shengchang Yang; Feifei Wang; Wenzhi Cao; Hui Yue; Shaoyun Peng (Applied Soil Ecology, 2024)

Capturing spatiotemporal heterogeneity in fertilizer application for better modelling paddy water nitrogen and phosphorus pollution at regional scale - Rui Ren; Huazhan Zhang; Xiang Gao; Housheng Wang; Wei Jiang; Yuhui Wang; Xiaosan Jiang; Zhaofu Li; Haiyan Zhao; Ganghua Li; Yanfeng Ding; Yue Mu (Agriculture, Ecosystems & Environment, 2024)

A new phthalides derivative pestalotiophthalide a with α-glucosidase inhibitory activity from Pestalotiopsis palmarum - Li-Bin Lin; Guang-Yu Bai; Xiang Zhao; Wei shi; Jia-Yao Hu; Jin-Ye Bai; Rui-Hua Wang; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Kinetic modeling of cell growth and value-added products accumulation of Thraustochytrium striatum - Rui Xiao; Zhaohui An; Xiang Li; Zhi-Wu Wang; Yi Zheng (Biomass and Bioenergy, 2024)

Tourism development potential and obstacle factors of cultural heritage: Evidence from traditional music in Xiangxi - Xianyong Zhang; Baofa Peng; Lulu Zhou; Chunyang Lu; Yali Wang; Rui Liu; Hui Xiang (Journal of Geographical Sciences, 2024)

Novel phenolic metabolites isolated from plant endophytic fungus Fusarium guttiforme - Jing-Yi Yue; Rui Wang; Tao Xu; Ju-Tao Wang; Yang Yu; Bai-Xiang Cai (Natural Product Research, 2024)

Evidence of transboundary movement of chemicals from Mexico to the U.S. in Tijuana River Estuary sediments - Flannery McLamb; Zuying Feng; Damian Shea; Kesten Bozinovic; Miguel F. Vasquez; Chris Stransky; Richard M. Gersberg; Wenling Wang; Xiang Kong; Xin-Rui Xia; Goran Bozinovic (Chemosphere, 2024)

Seasonal variations of microplastics in surface water and sediment in an inland river drinking water source in southern China - Wenyu Zhao; Jing Li; Mengyue Liu; Rui Wang; Boxuan Zhang; Xiang-Zhou Meng; Shengwei Zhang (Science of The Total Environment, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Tree-ring structured phase change materials with high through-plane thermal conductivity and flexibility for advanced thermal management - Wan-jun Jiang; Rui-qing Wang; Ting-yu Zhu; Mai Feng; De-xiang Sun; Jing-hui Yang; Xiao-dong Qi; Yong Wang (Chemical Engineering Journal, 2024)

Carbamazepine facilitated horizontal transfer of antibiotic resistance genes by enhancing microbial communication and aggregation - Yinping Xiang; Meiying Jia; Rui Xu; Jialu Xu; Lele He; Haihao Peng; Weimin Sun; Dongbo Wang; Weiping Xiong; Zhaohui Yang (Bioresource Technology, 2024)

Using 2DVD technology to explore droplet characteristic variations of sprinkler irrigation as affected by a maize canopy - Jian Wang; Yu Xiang; Rui Chen; Hong Li (Computers and Electronics in Agriculture, 2023)

Leaf spot on cucumber caused by Stemphylium vesicarium newly reported in China - Xiaoyan Yu; Rui Han; Weiqian Zhang; Zhihua Li; Xue Zhang; Xiangjing Wang; Wensheng Xiang; Junwei Zhao (Crop Protection, 2023)

Effects of Mixed Cropping on Sugarcane Growth and the Community of Arbuscular Mycorrhizal Fungi - Ying-Jie Nong; Qian Wang; Juan Song; Jin-Lian Zhang; Xiao-Juan Qin; Yi-Hao Kang; Xiang-Hua Wei; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Evaluating soil water movement and soil water content uniformity under sprinkler irrigation with different soil texture and irrigation uniformity using numerical simulation - Rui Chen; Hong Li; Jian Wang; Xin Guo; Yu Xiang (Journal of Hydrology, 2023)

Enzymatic characteristics and potential natural inhibitors of oat lipase - Yuting Xiang; Liang Zou; Rui Dong; Xiaolong Wang; Xinzhong Hu (Journal of Cereal Science, 2023)

Experimental study on enhanced coal seam gas extraction by uniform pressure/pulse pressure N2 injection - Peng-fei Ji; Hai-fei Lin; Xiang-guo Kong; Shu-gang Li; Yu-chu Cai; Rui-zhe Wang; Yu Tian; Tian-shuo Zhao (Fuel, 2023)

Surface engineered long-lasting antibacterial Janus cotton fabrics with excellent moisture/thermal management properties - Lujie Wang; Maoshuang Chen; Rui Cai; Jingjing Jiang; Shuangfei Xiang; Xiangdong Liu; Hongyan Diao (Chemical Engineering Journal, 2023)

Illustration on phenotypic and genotypic characteristics of typical multi-antibiotic resistant bacteria in aquatic environments through complete genomes and comparative genomics - Chunli Wan; Rui Tang; Liyan Deng; Liya Fu; Panxin Wang; Xiang Liu; Changyong Wu (Chemosphere, 2023)

Triterpenoid saponins from Psammosilene tunicoides and their antinociceptive activities - Yan-Hong Li; Xi-Shan Bai; Xiu-Xia Yang; Yu-Xiao Li; Hong-Rui Li; Zi-Liang Wang; Wei Wang; Kai Tian; Xiang-Zhong Huang (Phytochemistry, 2023)

Competitive photoelectrochemical aptamer sensor based on a Z-scheme Fe2O3/g-C3N4 heterojunction for sensitive detection of lead ions - Jingui Chen; Jinxiu Zhao; Rui Feng; Hongmin Ma; Huan Wang; Xiang Ren; Qin Wei; Huangxian Ju (Journal of Hazardous Materials, 2023)

Rethinking personal carbon trading (PCT) mechanism: A comprehensive review - Yun-En Tang; Ru Fan; Ang-Zu Cai; Le-Yi Wang; Rui-Min Lin; Xiang-Zhou Meng; Ling Chen; Ru Guo (Journal of Environmental Management, 2023)

Boosting PFOA photocatalytic removal from water using highly adsorptive and sunlight-responsive ZIF67/MIL-100(Fe) modified C3N4 - Peidong Su; Chunhui Zhang; Yu Liu; Junke Zhang; Ridha Djellabi; Rui Wang; Junqiang Guo; Rui Zhang; Hongwei Guo; Xiang Ding; Xinyue Liu (Journal of Environmental Chemical Engineering, 2023)

Risk factors for thrombocytopenia in patients receiving linezolid therapy: a systematic review and meta-analysis - Dan Zhang; Yasi Xu; Xiang Wang; Leping Hou; Mengyu Xing; Shuang Xu; Rui Guo; Ying Luo (European Journal of Clinical Pharmacology, 2023)

Effects of atrazine on microbial metabolic limitations in black soils: Evidence from enzyme stoichiometry - Tiancong Gao; Haixia Tian; Ziqi Wang; Jing Shi; Rui Yang; Fang Wang; Leilei Xiang; Yunchao Dai; Mallavarapu Megharaj; Wenxiang He (Chemosphere, 2023)

Adjusting effects of pyrolytic volatiles interaction in char to upgrade oil by swelling waste nylon-tire - Rui Huang; Qiangqiang Ren; Jialin Zhang; Limo He; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Song Hu; Jun Xiang (Waste Management, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

GRPR down-regulation inhibits spermatogenesis through Ca2+ mediated by PLCβ/IP3R signaling pathway in long-term formaldehyde-exposed rats - Yan-qi Yang; Rui-fang Sun; Pan Ge; Wen-Xing Li; Xiang Zhang; Jian Zhang; Lu Ye; Nan Zhang; Si-yu Wang; Mo-qi Lv; Dang-xia Zhou (Food and Chemical Toxicology, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

COS and H2S simultaneous removal from blast furnace gas over a tailored Cu/Zr co-doped K@TiO2 bifunctional catalyst under low temperature - Xiang Li; Xueqian Wang; Li Yuan; Langlang Wang; Yixing Ma; You Wu; Yibing Xie; Rui Cao; Yiran Xiong; Ping Ning (Chemical Engineering Journal, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

SymmetricNet: end-to-end mesoscale eddy detection with multi-modal data fusion - Yuxiao Zhao; Zhenlin Fan; Haitao Li; Rui Zhang; Wei Xiang; Shengke Wang; Guoqiang Zhong (Frontiers in Marine Science, 2023)
Mesoscale eddies play a significant role in marine energy and matter transportation. Due to their huge impact on the ocean, mesoscale eddy detection has been studied for many years. However, existing methods mainly use single-modal data, such as the sea surface height (SSH), to detect mesoscale eddies, resulting in inaccurate detection results. In this paper, we propose an end-to-end mesoscale eddy detection method based upon multi-modal data fusion. Particularly, we don’t only use SSH, but also add data of other two modals, i.e., the sea surface temperature (SST) and the velocity of flow, which are closely related to mesoscale eddy detection. Moreover, we design a novel network named SymmetricNet, which is able to achieve multi-modal data fusion in mesoscale eddy detection. The proposed SymmetricNet mainly contains a downsampling pathway and an upsampling pathway, where the low-level feature maps from the downsampling pathway and the high-level feature maps from the upsampling pathway are merged through lateral connections. In addition, we apply dilated convolutions to the network structure to increase the receptive field without sacrificing resolution. Experiments on multi-modal mesoscale eddy dataset demonstrate the advantages of the proposed method over previous approaches for mesoscale eddy detection.

Epicoccum sorghinum as leaf spot disease-causing pathogen in ginger (Zingiber officinale Rosc.) in China - Xiaoyan Yu; Zhihua Li; Rui Han; Weiqian Zhang; Jing Zhang; Weiyue Cao; Yue Ma; Xiangjing Wang; Junwei Zhao; Wensheng Xiang (Crop Protection, 2023)

Nano-pesticide carrier O-Carboxymethyl chitosan is indigestible in Apis cerana cerana and affects intestinal flora - Sheng-nan Li; Hao Wu; Rui-quan Hou; Jing-tong Zhou; Su-kun Lin; Kun-yu Zhao; Rui-fei Wang; Su-qing Huang; Zhi-xiang Zhang (Science of The Total Environment, 2023)

Experimental study on the influence of a T-foil and bulbous bow on the resistance and motion in regular head waves of trimarans - Rui Deng; Sichong Huang; Shigang Wang; Hailong Liu; Xiang Yu; Tiecheng Wu (Ocean Engineering, 2023)

Antibacterial, antiviral, and biodegradable collagen network mask for effective particulate removal and wireless breath monitoring - Peng Zhao; Rui Wang; Jun Xiang; Jinwei Zhang; Xiaodong Wu; Chaojian Chen; Gongyan Liu (Journal of Hazardous Materials, 2023)

Enhanced recovery of germanium(IV) from zinc residue leachate by tartaric acid functionalized chitosan: Experiments and DFT calculation - Hongrui Xiang; Zhihui Yang; Xiaobo Min; Yanjie Liang; Cong Peng; Xiaoyun Liu; Rui Yuan; Qingwei Wang; Feiping Zhao (Hydrometallurgy, 2023)

Nickel based catalyst supported by carbon aerogel prepared from waste pomelo peel to crack ethanol for hydrogen production: Catalytic performance and mechanism - Jialin Zhang; Song Hu; Yong Ding; Rui Huang; Qiangqiang Ren; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Jun Xiang (Fuel, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Pathogenicity characteristics of the entomopathogenic fungus Cordyceps javanica IJ-tg19 to Acyrthosiphon pisum - Di Wang; Pei-Xiang Xing; Hong-Liang Diao; Wen-Wen Zhou; Xian-Wei Li; Li-Jun Zhang; Rui-Yan Ma (BioControl, 2023)

Systematic exploration of transcriptional responses of interspecies interaction between Karenia mikimotoi and Prorocentrum shikokuense - Jian-Wei Zheng; Guo-Hui He; Rui-Xia Xu; Xiang Wang; Hong-Ye Li; Wei-Dong Yang (Harmful Algae, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Highly synergistic and polarized KNbO3/WO3 heterojunction for piezo-photocatalytic degradation of organic pollutant - Rui Huang; Wei Cai; Heng Zhang; Zhenhua Wang; Qin Zhang; Rongli Gao; Gang Chen; Xiaoling Deng; Xiang Lei; Jiling Dong; Xiaoyan Liu; Chunlin Fu (Journal of Environmental Chemical Engineering, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

Physicochemical Characterization of Three Active Pharmaceutical Ingredients for Compound Glycyrrhizin Solid Formulation and Compatibility Analysis via Thermal and Non-thermal Techniques - Xiang-yun Xie; Zhan-ying Chang; Chun-li Chen; Liang Zhang; Mei Wang; Cheng Tang; Hong-rui Xue; Xiao-li Gao (Journal of Pharmaceutical Innovation, 2023)

A testis-specific gene doublesex is involved in spermatogenesis and early sex differentiation of the Chinese mitten crab Eriocheir sinensis - Long Wang; Zhi-Qiang Liu; Ke-Yi Ma; Jing-Rui Tao; Xiang Fang; Gao-Feng Qiu (Aquaculture, 2023)

CuFe2O4/diatomite actuates peroxymonosulfate activation process: Mechanism for active species transformation and pesticide degradation - Peng Xu; Rui Wei; Peng Wang; Xiang Li; Chunyan Yang; Tianyao Shen; Tong Zheng; Guangshan Zhang (Water Research, 2023)

A quasi-one-dimensional bulk thermoelectrics with high performance near room temperature - Qingxin Dong; Junsen Xiang; Zhen Wang; Yunxiu Li; Rui Lu; Te Zhang; Nan Chen; Yifei Huang; Yiyan Wang; Wenliang Zhu; Guodong Li; Huaizhou Zhao; et al. (Science Bulletin, 2023)

Improvement of soybean meal quality by one-step fermentation with mixed-culture based on protease activity - Chuan Wang; Xiaozhi Qiu; Rui Hou; Jun Liu; Li Li; Xiang Mao (Innovative Food Science & Emerging Technologies, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Magnetic field assisted enhancement of electronic metal-support interactions in FexCuy@TiO2-δ catalysts for arsine catalytic oxidation - Yibing Xie; Xueqian Wang; Ping Ning; Langlang Wang; Yixing Ma; Yuan Li; Rui Cao; Hui Zhang; Xiang Li; Bowen Xu (Journal of Cleaner Production, 2023)

Advantageous Role of N-doping on K@Al in COS/CS2 Hydrolysis: Diminished Oxygen Mobility and Rich basic sites - Rui Cao; Xueqian Wang; Ping Ning; Yibing Xie; Langlang Wang; Yixing Ma; Xiang Li; Hui Zhang; Jingye Liu (Fuel, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

High adaptability and stability FeCo2O4/diatomite composite for efficient peroxymonosulfate activation: Performance, water matrix impact, and mechanism - Peng Xu; Xiang Li; Rui Wei; Chunyan Yang; Tianyao Shen; Peng Wang; Guangshan Zhang (Chemical Engineering Journal, 2023)

Modulation of the interfacial properties of TiN coatings to generate Rigid-Flexible SEI for better SiO anodes - Hebang Shi; He Zhang; Rui Wang; Ming Liu; Zihan Shen; Jingbo Chen; Binbin Wu; Maoqiao Xiang; Jun Li; Huigang Zhang; Pengpeng Lv; Qingshan Zhu (Chemical Engineering Journal, 2023)

Differences in the patterns and mechanisms of leaf and ecosystem-scale water use efficiencies on the Qinghai-Tibet Plateau - Xiang Wang; Guo Chen; Mingquan Wu; Xiaozhen Li; Qi Wu; Peng Wang; Hui Zeng; Rui Yang; Xiaolu Tang (CATENA, 2023)

P2Y12 receptor gene polymorphisms are associated with epilepsy - Qi Wang; Nan-Rui Shi; Peng Lv; Juan Liu; Ji-Zhou Zhang; Bin-Lu Deng; Yan-Qin Zuo; Jie Yang; Xin Wang; Xiang Chen; Xiu-Min Hu; Ting-Ting Liu; et al. (Purinergic Signalling, 2023)
The basic research indicated that microglial P2Y12 receptors ( P2Y12Rs ) are involved in the pathophysiology of epilepsy through regulated microglial-neuronal interactions, aberrant neurogenesis, or immature neuronal projections. However, whether the clinic case of epilepsy would be associated with P2Y12 receptor gene polymorphisms is presented with few data. In our study, a total of 176 patients with epilepsy and 50 healthy controls were enrolled. Two single-nucleotide polymorphisms, namely rs1491974 and rs6798347, were selected for analysis. The results revealed that carriers of the G allele of rs1491974 G>A or rs6798347 G>A may be associated with an increased risk of epilepsy (OR = 0.576, 95% CI = 0.368–0.901, p = 0.015; OR = 0.603, 95% CI = 0.367–0.988, p = 0.043). Interestingly, we found that the rs1491974 G>A genotype and allele frequencies have only a significant difference in female instead of male case ( p = 0.004 for genotype; p = 0.001 for allele). The subgroup analysis demonstrated that individuals with the rs1491974 G>A genotype might have more frequent seizure (OR = 0.476, 95% CI = 0.255–0.890; p = 0.019). These data implied that both rs1491974 and rs6798347 polymorphisms of P2Y12R would be able to play import roles in epilepsy susceptibility, whereas the rs1491974 polymorphism may be specifically related to seizure frequency.

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

A stomatal optimization model adopting a conservative strategy in response to soil moisture stress - Rui Zhu; Tiesong Hu; Quan Zhang; Xiang Zeng; Shan Zhou; Fengyan Wu; Yong Liu; Yanxuan Wang (Journal of Hydrology, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Analytical solutions on non-Darcy seepage of grouted and lined subsea tunnels under dynamic water levels - Xiang Liu; Dongchi Wang; Yu Zhang; Annan Jiang; Qian Fang; Rui Zhang (Ocean Engineering, 2023)

Permanent displacement reliability analysis of soil slopes subjected to mainshock-aftershock sequences - Gan Wang; Rui Pang; Xiang Yu; Bin Xu (Computers and Geotechnics, 2023)

Fluoroalkane modified cationic polymers for personalized mRNA cancer vaccines - Junyan Li; Yuanyuan Wu; Jian Xiang; Hairong Wang; Qi Zhuang; Ting Wei; Zhiqin Cao; Qingyang Gu; Zhuang Liu; Rui Peng (Chemical Engineering Journal, 2023)

Coexistence of microplastics alters the inhibitory effect of antibiotics on sludge anaerobic digestion - Yinping Xiang; Weiping Xiong; Zhaohui Yang; Rui Xu; Yanru Zhang; Mengru Wu; Yuhang Ye; Haihao Peng; Jing Tong; Dongbo Wang (Chemical Engineering Journal, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

Characteristics of stress, crack evolution, and energy conversion of anchored granite containing two preexisting fissures under uniaxial compression - Wen Guanping; Hu Jianhua; Wang Jie; Yang Dongjie; Xiang Rui (Bulletin of Engineering Geology and the Environment, 2023)

Characterizing diversity based on phenotypes and molecular marker analyses of purple yam (Dioscorea alata L.) germplasm in southern China - Xin Chen; Jingyu Sun; Qianglong Zhu; Yao Xiao; Hongyu Zhang; Yingjin Huang; Putao Wang; Tianxu Cao; Rui Hu; Zijin Xiang; Nan Shan; Qinghong Zhou (Genetic Resources and Crop Evolution, 2022)

Research on PEMS Test Data Processing Method and Cold Start Emission Evaluation Method of Heavy-Duty Diesel Vehicles - Gangzhi Tang; Shuaibin Wang; Rui Wang; Baocheng Du; Yu Liu; Gang Tian; Linyao Ran; Gan Xiang; Huang Li (Water, Air, & Soil Pollution, 2022)

miR-517b-3p promotes the progression of portal vein tumor thrombus via activating Wnt/β-catenin signaling pathway in hepatocellular carcinoma - Rui-Sheng Ke; Kun-Zhai Huang; De-sheng Bao; Jing-Rui Yang; Hua-xiang Wang; Li-Zhi Lv; Yi Jiang; Zhao-Hui Liu; Fu-Xing Zhang (Molecular Biology Reports, 2022)

Validation of reliable safe harbor locus for efficient porcine transgenesis - Xiang Ma; Weijun Zeng; Lei Wang; Rui Cheng; Zeying Zhao; Caiyun Huang; Zhongxin Sun; Peipei Tao; Tao Wang; Jufang Zhang; Lu Liu; Xing Duan; et al. (Functional & Integrative Genomics, 2022)

Hierarchical collagen fibers complexed with tannic acid and Fe3+ as a heterogeneous catalyst for enhancing sulfate radical-based advanced oxidation process - Rui Wang; Ruiquan Yu; Junchao Wang; Jun Xiang; Chaojian Chen; Gongyan Liu; Xuepin Liao (Environmental Science and Pollution Research, 2022)

Synthesis of hollow mesoporous silica spheres functionalized with copper ferrocyanide and its application for Cs+ removal - Xiaoying Peng; Jiahao Zheng; Jinsong Wang; Chao Xiang; Rui Wang (Environmental Science and Pollution Research, 2022)

Trophic Niche Partitioning of Five Sciaenidae Species Sampled in Zhoushan Archipelago Waters via Stable Isotope Analysis - Jing Wang; Ri-Jin Jiang; Yi Xiao; Rui Yin; Feng Chen; Yong-dong Zhou; Han-Xiang Xu (Frontiers in Marine Science, 2022)
Sciaenid fishes are usually associated with large freshwater inputs and are the most important economic fish on the coastal shelf off mainland China. To compare the differences in ecological niche and resource sharing among different populations of Sciaenidae species, we collected samples of Larimichthys polyactis , Collichthys lucidus , Johnius belangerii , Nibea albiflora , and Miichthys miiuy from Zhoushan Archipelago waters from 2019 to 2021 and investigated the carbon and nitrogen isotopic values in muscle tissues, the contribution of each food resource, and trophic niche widths and overlaps. Significant differences were observed in both isotopes in the muscles of the five Sciaenid species. Zooplankton was a key food resource for all Sciaenid species. In addition to zooplankton, J. belangerii , N. albiflora , and M. miiuy also fed on benthos organisms. C. lucidus presented a wide trophic niche width and had extensive habitat use. The trophic niche occupied by N. albiflora and M. miiuy was narrow; they presented a high trophic level, with a high degree of trophic niche overlap. This study showed that sciaenid fishes have overlapping trophic niches due to their common feeding on zooplankton, and differences in body size, migration, habitat, and feeding choices led to the reasonable sharing of resources among the five sciaenid fishes, allowing the coexistence of these species.

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

Chlorogenic acid, a natural product as potential inhibitor of COVID-19: virtual screening experiment based on network pharmacology and molecular docking - Wen-Xiang Wang; Ying-Rui Zhang; Shi-Ying Luo; Yun-Sen Zhang; Yi Zhang; Ce Tang (Natural Product Research, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Secondary metabolites isolated from Agrimonia pilosa Ledeb. - Hong-Rui Li; Yu-Kui Li; Jian Xiao; Cui Yang; Meng-Yuan Jiang; Kai Tian; Wei Wang; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2022)

Enhanced stripe rust resistance obtained by combining Yr30 with a widely dispersed, consistent QTL on chromosome arm 4BL - Shengjie Liu; Xiaoting Wang; Yayun Zhang; Yangang Jin; Zhonghua Xia; Mingjie Xiang; Shuo Huang; Linyi Qiao; Weijun Zheng; Qingdong Zeng; Qilin Wang; Rui Yu; et al. (Theoretical and Applied Genetics, 2022)

Laser ablation inductively coupled plasma mass spectrometry analysis of Chinese lead-barium glass: combining multivariate kernel density estimation and maximum mean discrepancy to reinterpret the raw glass used for producing lead-barium glass - Qian Ma; Rui Wen; Yifan Yu; Long Wang; Man Li; Luwu Cai; Li Ping; Zhiqiang Zhao; Dong Wang; Xiang Wang; Ruoyu Shi; A. Mark Pollard (Archaeological and Anthropological Sciences, 2022)

Seasonal fluctuation of aerosolization ratio of bioaerosols and quantitative microbial risk assessment in a wastewater treatment plant - Rui-ning Wang; Xiang Li; Cheng Yan (Environmental Science and Pollution Research, 2021)

Characteristics of Ichthyoplankton Communities and Their Relationship With Environmental Factors Above the Ninety East Ridge, Eastern Indian Ocean - Liyan Zhang; Jing Zhang; Shigang Liu; Rui Wang; Jiali Xiang; Xing Miao; Ran Zhang; Puqing Song; Longshan Lin (Frontiers in Marine Science, 2021)
The Ninety East Ridge is a submarine north–south oriented volcanic ridge in the eastern Indian Ocean. Surface-layer ichthyoplankton collected in this area from September to October were identified by combined morphological and molecular (DNA barcoding) techniques, and their species composition, diversity, and abundance, and correlations with environmental variables were described. Collections comprised 109 larvae and 507 eggs, which were identified to 37 taxa in 7 orders, 20 families, and 27 genera, and were dominated by the order Perciformes and species Vinciguerria sp., Oxyporhamphus micropterus , and Decapterus macarellus . Species abundances at each station and of each species were relatively low, suggesting that this area or the time of sampling were not of major importance for fish spawning. Waters above Ninety East Ridge had lower species diversity but higher species richness than waters further offshore. A generalized additive model revealed that high abundance of ichthyoplanktonic taxa occurred in areas with low sea surface height and high sea surface salinity, temperature, and chlorophyll a concentration. Of these, sea surface height was most correlated with ichthyoplankton abundance. We provided baseline data on surface-dwelling ichthyoplankton communities in this area to aid in development of pelagic fishery resources in waters around the Ninety East Ridge.

Overexpression of MdPHR1 Enhanced Tolerance to Phosphorus Deficiency by Increasing MdPAP10 Transcription in Apple (Malus × Domestica) - Rui Li; Jian-Ping An; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Journal of Plant Growth Regulation, 2021)

Distinctive distributions of halophilic Archaea across hypersaline environments within the Qaidam Basin of China - Derui Zhu; Guoping Shen; Zhibo Wang; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Yongzhen Li; Rong Wang (Archives of Microbiology, 2021)

The influence of partial pile cutting on the pile-anchor supporting system of deep foundation pit in loess area - Yunxin Zheng; Zhiping Hu; Xiang Ren; Rui Wang; Enxiang Zhang (Arabian Journal of Geosciences, 2021)

Effects of Tobacco Stem-Derived Biochar on Soil Properties and Bacterial Community Structure under Continuous Cropping of Bletilla striata - Linyan Zhao; Huilin Guan; Rui Wang; Haoji Wang; Zecheng Li; Wei Li; Ping Xiang; Wumei Xu (Journal of Soil Science and Plant Nutrition, 2021)

Nitrogen fertilization overweighs intercropping in promotion of dissolved organic carbon concentration and complexity in potato-cropped soil - Ding Wang; Ping Zhao; Rui Xiang; Shuran He; Yanli Zhou; Xinhua Yin; Guangqiang Long (Plant and Soil, 2021)

Herbidospora solisilvae sp. nov., a novel cellulose-degrading actinobacterium isolated from forest soil - Mingying Yu; Rui Zhou; Jingjing Li; Liyuan Han; Han Wang; Siyu Zhang; Junwei Zhao; Xiangjing Wang; Jia Song; Wensheng Xiang (Antonie van Leeuwenhoek, 2021)

A Rehmannia glutinosa cinnamate 4-hydroxylase promotes phenolic accumulation and enhances tolerance to oxidative stress - Yan Hui Yang; Heng Yang; Rui Fang Li; Cui Xiang Li; Lei Zeng; Chao Jie Wang; Na Li; Zhuang Luo (Plant Cell Reports, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Down-regulation of SETD6 protects podocyte against high glucose and palmitic acid-induced apoptosis, and mitochondrial dysfunction via activating Nrf2-Keap1 signaling pathway in diabetic nephropathy - Xiang Wang; Qiling Liu; Deqin Kong; Zi Long; YuFang Guo; Shuang Wang; Rui Liu; Chunxu Hai (Journal of Molecular Histology, 2020)

Graph-based network analysis of resting-state fMRI: test-retest reliability of binarized and weighted networks - Jie Xiang; Jiayue Xue; Hao Guo; Dandan Li; Xiaohong Cui; Yan Niu; Ting Yan; Rui Cao; Yao Ma; Yanli Yang; Bin Wang (Brain Imaging and Behavior, 2020)

Evaluating Spatial Heterogeneity of Land Surface Hydrothermal Conditions in the Heihe River Basin - Yuan Zhang; Shaomin Liu; Xiao Hu; Jianghao Wang; Xiang Li; Ziwei Xu; Yanfei Ma; Rui Liu; Tongren Xu; Xiaofan Yang (Chinese Geographical Science, 2020)

An evaluation of the core bacterial communities associated with hypersaline environments in the Qaidam Basin, China - Derui Zhu; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Guoping Shen; Yongzhen Li; Rong Wang (Archives of Microbiology, 2020)

Formation of nano- or near-nanoparticles via oxidation in the Dabaoshan concealed deposit, Guangdong Province - Rui Liu; Jianjin Cao; Yongkang Deng; Guoqiang Wang; Xiang Liu (Arabian Journal of Geosciences, 2020)

Bacterial and Archaeal Communities within an Ultraoligotrophic, High-altitude Lake in the Pre-Himalayas of the Qinghai-Tibet Plateau - Rong Wang; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Guoping Shen; Derui Zhu (Indian Journal of Microbiology, 2020)

A Moso bamboo gene VQ28 confers salt tolerance to transgenic Arabidopsis plants - Xinran Cheng; Yujiao Wang; Rui Xiong; Yameng Gao; Hanwei Yan; Yan Xiang (Planta, 2020)

Development of 19 novel microsatellite markers of lily-of-the-valley (Convallaria, Asparagaceae) from transcriptome sequencing - Qi-Xiang Lu; Jing Gao; Jun-Jie Wu; Xuan Zhou; Xue Wu; Meng-Di Li; Yu-Kun Wei; Rui-Hong Wang; Zhe-Chen Qi; Pan Li (Molecular Biology Reports, 2020)

Molecular cloning and functional characterization of the CEP RECEPTOR 1 gene MdCEPR1 of Apple (Malus × domestica) - Rui Li; Jian-Ping An; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Separating and imaging diffractions in dip domain on the basis of slope analysis - Xue Kong; De-Ying Wang; Zhen-Chun Li; Rui-Xiang Zhang; Qiu-Yuan Hu (Applied Geophysics, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Efficient generation of GHR knockout Bama minipig fibroblast cells using CRISPR/Cas9-mediated gene editing - Rui Wang; Jian-Ying Zhang; Ke-Huan Lu; Sheng-Sheng Lu; Xiang-Xing Zhu (In Vitro Cellular & Developmental Biology - Animal, 2019)

Design and Experiment of a Plateau Data-Gathering AUV - Hao Xu; Guo-Cheng Zhang; Yu-Shan Sun; Shuo Pang; Xiang-Rui Ran; Xiang-Bin Wang (Journal of Marine Science and Engineering, 2019)
The design, control, and implementation of an autonomous underwater vehicle (AUV) for collecting hydrological information from plateau rivers and lakes are presented in this paper. The hardware and software structures of the control system were previously described. A novel sliding mode controller (SMC) with combinational reaching law of vertical hovering motion is proposed to improve the robustness and stability. The S-plane control, a nonlinear controller with little parameters, is used in the horizontal motion. Besides, the navigation strategy based on the dead-reckoning algorithm, a path tracking based on the light-of-sight (LOS) algorithm, and a control allocation strategy considering saturation are present. Finally, experiments were performed in a tank and in a river in the Qinghai–Tibet Plateau to prove the feasibility and reliability of the AUV system.

Overexpression of AtAGT1 promoted root growth and development during seedling establishment - Rui Wang; Lin Yang; Xiaofang Han; Yuhong Zhao; Ling Zhao; Beibei Xiang; Yerong Zhu; Yanling Bai; Yong Wang (Plant Cell Reports, 2019)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

Growth Inhibiting Effects of Four Antibiotics on Cucumber, Rape and Chinese Cabbage - Rui Wang; Jun Wang; Jinhua Wang; Lusheng Zhu; Wenjie Zhang; Xiang Zhao; Zulfiqar Ahmad (Bulletin of Environmental Contamination and Toxicology, 2019)

Nanoparticles: Oral Delivery for Protein and Peptide Drugs - Shu-jun Cao; Shuo Xu; Hui-ming Wang; Yong Ling; Jiahua Dong; Rui-dong Xia; Xiang-hong Sun (AAPS PharmSciTech, 2019)

Reduced hemispheric asymmetry of brain anatomical networks in attention deficit hyperactivity disorder - Dandan Li; Ting Li; Yan Niu; Jie Xiang; Rui Cao; Bo Liu; Hui Zhang; Bin Wang (Brain Imaging and Behavior, 2019)

Development of a colloidal gold-based immunochromatographic strip for rapid detection of Rice stripe virus - De-qing Huang; Rui Chen; Ya-qin Wang; Jian Hong; Xue-ping Zhou; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2019)

Enhanced water solubility, antioxidant activity, and oral absorption of hesperetin by D-α-tocopheryl polyethylene glycol 1000 succinate and phosphatidylcholine - Su-Fang Gu; Li-Ying Wang; Ying-Jie Tian; Zhu-Xian Zhou; Jian-Bin Tang; Xiang-Rui Liu; Hai-Ping Jiang; You-Qing Shen (Journal of Zhejiang University-SCIENCE B, 2019)

Lappaconitine, a C18-diterpenoid alkaloid, exhibits antihypersensitivity in chronic pain through stimulation of spinal dynorphin A expression - Ming-Li Sun; Jun-Ping Ao; Yi-Rui Wang; Qian Huang; Teng-Fei Li; Xin-Yan Li; Yong-Xiang Wang (Psychopharmacology, 2018)

Use of cationic microbubbles targeted to P-selectin to improve ultrasound-mediated gene transfection of hVEGF165 to the ischemic myocardium - Wei-hui Shentu; Cao-xin Yan; Chun-mei Liu; Rui-xiang Qi; Yao Wang; Zhao-xu Huang; Li-ming Zhou; Xiang-dong You (Journal of Zhejiang University-SCIENCE B, 2018)

Genome-wide analysis and identification of the SMXL gene family in apple (Malus × domestica) - Rui Li; Jian-Ping An; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Tree Genetics & Genomes, 2018)

Assessing the influence of climate change and inter-basin water diversion on Haihe River basin, eastern China: a coupled model approach - Jun Xia; Qiang Wang; Xiang Zhang; Rui Wang; Dunxian She (Hydrogeology Journal, 2018)

Temporal and Spatial Variations of Microbial Carbon Utilization in Water Bodies from the Dajiuhu Peatland, Central China - Rui-Cheng Wang; Hong-Mei Wang; Xing Xiang; Yu Gao; Qing-Wei Song; Lin-Feng Gong (Journal of Earth Science, 2018)

Hi1a as a Novel Neuroprotective Agent for Ischemic Stroke by Inhibition of Acid-Sensing Ion Channel 1a - Yandong Ren; Chengchong Li; Jinlong Chang; Rui Wang; Yuhua Wang; Xiang-Ping Chu (Translational Stroke Research, 2018)

A Fluorescent Sensor of 3-Aminobenzeneboronic Acid Functionalized Hydrothermal Carbon Spheres for Facility Detection of L-tryptophan - Rui Zhang; Li-Xia Wang; Yun-Di Zhang; Chun-Hua Ge; Jia-Ping Wang; Ying Zhang; Xiang-Dong Zhang (Journal of Fluorescence, 2018)

ABA pretreatment enhances the chilling tolerance of a chilling-sensitive rice cultivar - Xiang Hongtao; Wang Tongtong; Zheng Dianfeng; Wang Lizhi; Feng Yanjiang; Luo Yu; Li Rui; Li Zhongjie; Meng Ying; Li Wan; Wang Lianmin; Yang Chunjie (Brazilian Journal of Botany, 2017)

Isolation and complete genome sequence of Halorientalis hydrocarbonoclasticus sp. nov., a hydrocarbon-degrading haloarchaeon - Dahe Zhao; Sumit Kumar; Jian Zhou; Rui Wang; Ming Li; Hua Xiang (Extremophiles, 2017)

Cold-Inducible Protein RBM3 Protects UV Irradiation-Induced Apoptosis in Neuroblastoma Cells by Affecting p38 and JNK Pathways and Bcl2 Family Proteins - Rui-Juan Zhuang; Jian Ma; Xiang Shi; Fei Ju; Shuang-Ping Ma; Lei Wang; Bin-Feng Cheng; Yan-Wen Ma; Mian Wang; Tong Li; Zhi-Wei Feng; Hai-Jie Yang (Journal of Molecular Neuroscience, 2017)

Diffraction separation by plane-wave prediction filtering - Xue Kong; De-Ying Wang; Zhen-Chun Li; Rui-Xiang Zhang; Qiu-Yuan Hu (Applied Geophysics, 2017)

Genesis and tectonic setting of the Late Devonian Tawuerbieke gold deposit in the Tulasu ore cluster, western Tianshan, Xinjiang, China - Yi-Wei Peng; Xue-Xiang Gu; Peng-Rui Lv; Yong-Mei Zhang; Wen-Bin Cheng; Xin-Li Wang (International Geology Review, 2017)

Glycyrrhizin inhibits porcine epidemic diarrhea virus infection and attenuates the proinflammatory responses by inhibition of high mobility group box-1 protein - Chang-chao Huan; Hua-xia Wang; Xiang-xiang Sheng; Rui Wang; Xin Wang; Xiang Mao (Archives of Virology, 2017)

Reduction of soil-borne pathogen Fusarium solani reproduction in soil enriched with phenolic acids by inoculation of endophytic fungus Phomopsis liquidambari - Xing-Guang Xie; Chuan-Chao Dai; Xiao-Gang Li; Jia-Rui Wu; Qing-Qian Wu; Xing-Xiang Wang (BioControl, 2017)

Molecular cloning and characterization of α-amylase/subtilisin inhibitor from rhizome of Ligusticum chuanxiong - Ji-hua Yu; Yang-yang Li; Mian Xiang; Jian-quan Zhu; Xin-he Huang; Wan-Jun Wang; Rui Tan; Jia-yu Zhou; Hai Liao (Biotechnology Letters, 2017)

Submerged macrophytes shape the abundance and diversity of bacterial denitrifiers in bacterioplankton and epiphyton in the Shallow Fresh Lake Taihu, China - Zhou Fan; Rui-ming Han; Jie Ma; Guo-xiang Wang (Environmental Science and Pollution Research, 2016)

Xenoliths in ultrapotassic volcanic rocks in the Lhasa block: direct evidence for crust–mantle mixing and metamorphism in the deep crust - Rui Wang; William J. Collins; Roberto F. Weinberg; Jin-xiang Li; Qiu-yun Li; Wen-yan He; Jeremy P. Richards; Zengqian Hou; Li-min Zhou; Richard A. Stern (Contributions to Mineralogy and Petrology, 2016)

Dynamics of Dissolved Oxygen and the Affecting Factors in Sediment of Polluted Urban Rivers under Aeration Treatment - Bo Liu; Wen-lin Wang; Rui-ming Han; Ming Sheng; Lin-lin Ye; Xu Du; Xin-ting Wu; Guo-xiang Wang (Water, Air, & Soil Pollution, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Association between the MTHFR A1298C polymorphism and risk of cancer: evidence from 265 case–control studies - Xin-Li Zhu; Zhi-Zhong Liu; Sen-Xiang Yan; Wei Wang; Rui-Xia Chang; Chun-Yan Zhang; Yan Guo (Molecular Genetics and Genomics, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

Adaptation to climate change impacts on water demand - Xiao-jun Wang; Jian-yun Zhang; Shamsuddin Shahid; En-hong Guan; Yong-xiang Wu; Juan Gao; Rui-min He (Mitigation and Adaptation Strategies for Global Change, 2016)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

Porcine epidemic diarrhea virus uses cell-surface heparan sulfate as an attachment factor - Chang-chao Huan; Yue Wang; Bo Ni; Rui Wang; Li Huang; Xiao-feng Ren; Guang-zhi Tong; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2015)

Review and evaluation of China’s standards and regulations on the fuel consumption of motor vehicles - Yue-Fu Jin; Zhao Wang; Hui-Ming Gong; Tian-Lei Zheng; Xiang Bao; Jia-Rui Fan; Michael Wang; Miao Guo (Mitigation and Adaptation Strategies for Global Change, 2015)

PtAKT1 maintains selective absorption capacity for K+ over Na+ in halophyte Puccinellia tenuiflora under salt stress - Pei Wang; Qiang Guo; Qian Wang; Xiang-Rui Zhou; Suo-Min Wang (Acta Physiologiae Plantarum, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Transcriptome profiling of biliary atresia from new born infants by deep sequencing - Jie Xiao; Su-yun Xia; Yun Xia; Qiang Xia; Xiang-rui Wang (Molecular Biology Reports, 2014)

Semicarbazide – from state-of-the-art analytical methods and exposure to toxicity: a review - Wen-Rui Tian; Ya-Xin Sang; Xiang-Hong Wang (Food Additives & Contaminants: Part A, 2014)

Two new cadinane-type sesquiterpenes from the Chinese liverwort Frullania serrata - Rui-Juan Li; Rong-Xiu Zhu; Yu Zhao; Susan L. Morris-Natschke; Chin-Ho Chen; Song Wang; Jiao-Zhen Zhang; Jin-Chuan Zhou; Hong-Xiang Lou; Kuo-Hsiung Lee (Natural Product Research, 2014)

Isolation and characterization of twenty-three polymorphic microsatellite loci in Schizothorax macropogon - Xiang-Zhao Guo; Gui-Rong Zhang; Ruo-Jin Yan; Wei Ji; Rui-Bin Yang; Kai-Jian Wei; Deng-Qiang Wang (Conservation Genetics Resources, 2014)

Tropomyosin-related kinase B promotes distant metastasis of colorectal cancer through protein kinase B-mediated anoikis suppression and correlates with poor prognosis - Meng Fan; Jianyong Sun; Wei Wang; Jing Fan; Lei Wang; Xiang Zhang; Angang Yang; Weizhong Wang; Rui Zhang; Jipeng Li (Apoptosis, 2014)

Effects of bromide and iodide ions on the formation of disinfection by-products during ozonation and subsequent chlorination of water containing biological source matters - Xiao-song Zha; Yan Liu; Xiang Liu; Qiang Zhang; Rui-hua Dai; Ling-wen Ying; Jin Wu; Jing-ting Wang; Luming Ma (Environmental Science and Pollution Research, 2014)

CTLA-4 polymorphisms and systemic lupus erythematosus (SLE): a meta-analysis - Jin-Xia Zhai; Li-Wei Zou; Zhao-Xiang Zhang; Wen-Jing Fan; Han-Yong Wang; Ting Liu; Zheng Ren; Rui-Xue Dai; Dongqing Ye (Molecular Biology Reports, 2013)

Comprehensive identification of high-frequency and co-occurring Mafa-DPA1, Mafa-DQA1, Mafa-DRA, and Mafa-DOA alleles in Vietnamese cynomolgus macaques - Ruirui Xiang; Huiling Zhang; Qing Deng; Rui Yue; Haite Tang; Yanqi Zhang; Fei Ling; Min Zhuo; Hongli Du; Shiqian Xu; Qiang Xu; Xiaoning Wang (Immunogenetics, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Expression profiles of Th17 pathway related genes in human systemic lupus erythematosus - Hai-Feng Pan; Rui-Xue Leng; Chen-Chen Feng; Xiang-Pei Li; Gui-Mei Chen; Bao-Zhu Li; Wang-Dong Xu; Song Guo Zheng; Dong-Qing Ye (Molecular Biology Reports, 2013)

Association of AFF1 rs340630 and AFF3 rs10865035 polymorphisms with systemic lupus erythematosus in a Chinese population - Han Cen; Rui-Xue Leng; Wei Wang; Mo Zhou; Chen-Chen Feng; Gui-Mei Chen; Rui Li; Hai-Feng Pan; Xiang-Pei Li; Dong-Qing Ye (Immunogenetics, 2012)

Does glyphosate impact on Cu uptake by, and toxicity to, the earthworm Eisenia fetida? - Chui-Fan Zhou; Yu-Jun Wang; Yuan-Chun Yu; Rui-Juan Sun; Xiang-Dong Zhu; Hai-Lin Zhang; Dong-Mei Zhou (Ecotoxicology, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Development of SSR markers for typing cultivars in the mushroom Auricularia auricula-judae - Rui Ying Zhang; Dan Dan Hu; Jin Gang Gu; Qing Xiu Hu; Xue Mei Zuo; He Xiang Wang (Mycological Progress, 2012)

Assessment of spatial distribution of soil loss over the upper basin of Miyun reservoir in China based on RS and GIS techniques - Tao Chen; Rui-qing Niu; Yi Wang; Ping-xiang Li; Liang-pei Zhang; Bo Du (Environmental Monitoring and Assessment, 2011)

Localized Delivery of Antisense Oligonucleotides by Cationic Hydrogel Suppresses TNF-α Expression and Endotoxin-Induced Osteolysis - Lei Dong; Zhen Huang; Xing Cai; Jiawei Xiang; Yi-An Zhu; Rui Wang; Jiangning Chen; Junfeng Zhang (Pharmaceutical Research, 2011)

Nicotinic acetylcholine receptor alpha7 subunit is time-dependently expressed in distinct cell types during skin wound healing in mice - Yan-Yan Fan; Tian-Shui Yu; Tao Wang; Wei-Wei Liu; Rui Zhao; Shu-Tao Zhang; Wen-Xiang Ma; Ji-Long Zheng; Da-Wei Guan (Histochemistry and Cell Biology, 2011)

PTEN status is related to cell proliferation and self-renewal independent of CD133 phenotype in the glioma-initiating cells - Ru-Bin Cheng; Rui-Juan Ma; Zhao-Kai Wang; Shan-Jun Yang; Xiang-Zhi Lin; Hui Rong; Yong Ma (Molecular and Cellular Biochemistry, 2011)

Evaluation of Genetic Manipulation Strategies on d-Lactate Production by Escherichia coli - Li Zhou; Zhi-Rui Zuo; Xian-Zhong Chen; Dan-Dan Niu; Kang-Ming Tian; Bernard A. Prior; Wei Shen; Gui-Yang Shi; Suren Singh; Zheng-Xiang Wang (Current Microbiology, 2011)

Genome-wide identification and evaluation of novel internal control genes for Q-PCR based transcript normalization in wheat - Xiang-Yu Long; Ji-Rui Wang; Thérèse Ouellet; Hélène Rocheleau; Yu-Ming Wei; Zhi-En Pu; Qian-Tao Jiang; Xiu-Jing Lan; You-Liang Zheng (Plant Molecular Biology, 2010)

Isolation and characterization of a gene encoding a polyethylene glycol-induced cysteine protease in common wheat - Qing-Wei Zang; Cai-Xiang Wang; Xu-Yan Li; Zhi-Ai Guo; Rui-Lian Jing; Jun Zhao; Xiao-Ping Chang (Journal of Biosciences, 2010)

Isolation and characterization of microsatellite markers from Lagerstroemia caudata (Lythraceae) and cross-amplification in other related species - Ming Cai; Rui Meng; Hui-Tang Pan; Yi-Ke Gao; Ming Sun; Ping Song; Xue-Feng Wang; Qi-Xiang Zhang (Conservation Genetics Resources, 2010)

Research development of the pathogenesis pathways for neuroschistosomiasis - Peng Wang; Ming-Can Wu; Shi-Jie Chen; Guo-Cai Luo; Xiang-Ling Cheng; Zhan-Sheng Zhu; Guang-Rui Zhao (Neuroscience Bulletin, 2010)

Expression and characterization of Momordica Chanrantia anti-hyperglycaemic peptide in Escherichia coli - Si-Xiu Liu; Zhong-Ping Fu; Rui-Min Mu; Zhi-Bi Hu; Fu-Jun Wang; Xiang-Rong Wang (Molecular Biology Reports, 2010)

Microbial community structure and diversity in a native forest wood-decomposed hollow-stump ecosystem - Bao-Yu Tian; Qin-Geng Huang; Yan Xu; Chun-Xiang Wang; Rui-Rui Lv; Jian-Zhong Huang (World Journal of Microbiology and Biotechnology, 2010)

Scutellarin exerts its anti-hypertrophic effects via suppressing the Ca2+-mediated calcineurin and CaMKII signaling pathways - Zhen-Wei Pan; Ying Zhang; Dong-Hua Mei; Rui Zhang; Jing-Hao Wang; Xiang-Ying Zhang; Chang-Qing Xu; Yan-Jie Lu; Bao-Feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

Complete genomic sequence analyses of Turnip mosaic virus basal-BR isolates from China - Hong-Yan Wang; Jin-Liang Liu; Rui Gao; Jia Chen; Yun-Hua Shao; Xiang-Dong Li (Virus Genes, 2009)

Identification and characterization of cyclin X which activates transcriptional activities of c-Myc - Xuanyang Li; Xiang Wang; Guoyuan Liu; Rui Li; Long Yu (Molecular Biology Reports, 2009)

Expression of a grape calcium-dependent protein kinase ACPK1 in Arabidopsis thaliana promotes plant growth and confers abscisic acid-hypersensitivity in germination, postgermination growth, and stomatal movement - Xiang-Chun Yu; Sai-Yong Zhu; Gui-Feng Gao; Xiao-Jing Wang; Rui Zhao; Ke-Qin Zou; Xiao-Fang Wang; Xiao-Yan Zhang; Fu-Qing Wu; Chang-Cao Peng; Da-Peng Zhang (Plant Molecular Biology, 2007)

Changes of Bt Toxin in the Rhizosphere of Transgenic Bt Cotton and its Influence on Soil Functional Bacteria - Yu-Kui Rui; Guo-Xiang Yi; Jing Zhao; Bao-Min Wang; Zhao-Hu Li; Zhi-Xi Zhai; Zhong-Pei He; Qing X. Li (World Journal of Microbiology and Biotechnology, 2005)

Identification of a novel rice bZIP-type transcription factor gene,OsbZIP1, involved in response to infection ofMagnaporthe grisea - Xiang-Bing Meng; Wen-Sheng Zhao; Rui-Ming Lin; Min Wang; You-Liang Peng (Plant Molecular Biology Reporter, 2005)

Genetic diversity in the Chinese pangolin (Manis pentadactyla) inferred from protein electrophoresis - Bing Su; Rui-Qing Liu; Ying-xiang Wang; Li-ming Shi (Biochemical Genetics, 1994)

Genetic diversity in the Chinese pangolin (Manis pentadactyla) inferred from protein electrophoresis - Bing Su; Rui-Qing Liu; Ying-xiang Wang; Li-ming Shi (Biochemical Genetics, 1994)